Packaging material for battery and battery

JP2025023243AInactive Publication Date: 2025-02-14DAI NIPPON PRINTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024210709
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2017-08-02
Filing Date
2024-12-03
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、少なくとも、基材層、バリア層、及び熱融着性樹脂層をこの順に備える積層体からなる電池用包装材料において、積層体の厚みが100μm以下と非常に薄いにも拘わらず、積層体の前記試験条件にて引張試験を行った際に計測される、「測定荷重(N/15mm)-変位量」の曲線から算出される単位幅1m当りの破断エネルギーについて、積層体の厚み方向とは垂直方向の一方向の前記破断エネルギーXと、前記一方向及び前記積層体の厚み方向の双方と垂直方向である他方向の前記破断エネルギーYの合計X+Yが、200J以上であることにより、成形性に優れた電池用包装材料を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023243000009
    Figure 2025023243000009
  • Figure 2025023243000010
    Figure 2025023243000010
  • Figure 2025023243000011
    Figure 2025023243000011
Patent Text Reader

Abstract

To provide a packaging material for a battery that is composed of a laminate having at least a base material layer, a barrier layer and a heat fusible resin layer in this order, which is excellent in moldability.SOLUTION: A packaging material for a battery is composed of a laminate having at least a base material layer, a barrier layer and a heat fusible resin layer in this order, wherein a thickness of the laminate is 100 μm or less, and in the laminate, as for breaking energy per unit width of 1 m calculated from a curve of a measurement load (N / 15 mm) and a displacement amount, which is measured when a tensile test is performed under the following test condition, X+Y of the total of breaking energy X in one direction perpendicular to a thickness direction of the laminate and breaking energy Y in the other direction perpendicular to both the one direction and the thickness direction of the laminate is 200 J or more. (Test condition) test speed: 50 mm / min, a width of a test piece: 15 mm, and a distance between gauge marks: 30 mm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a packaging material for a battery and a battery. [Background technology]

[0002] Various types of batteries have been developed, but packaging materials are essential components for all batteries to seal battery elements such as electrodes and electrolytes. Conventionally, metallic packaging materials have been widely used for battery packaging.

[0003] Meanwhile, in recent years, batteries are being required to have a variety of shapes and to be thin and lightweight in line with the increasing performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc. However, the metallic battery packaging materials that have been widely used in the past have the drawbacks of being difficult to keep up with the diversification of shapes and also having limitations in terms of weight reduction.

[0004] In recent years, a film-like laminate in which a base material layer, a barrier layer, and a heat-sealable resin layer are laminated in this order has been proposed as a packaging material for batteries that can be easily processed into a variety of shapes and can be made thinner and lighter (see, for example, Patent Document 1).

[0005] In such a battery packaging material, generally, a recess is formed by cold forming, and battery elements such as electrodes and an electrolyte are arranged in the space formed by the recess, and the heat-sealable resin layers are heat-sealed to each other to obtain a battery in which the battery elements are accommodated inside the battery packaging material. However, such a film-like packaging material is thinner than a metal packaging material, and has the disadvantage that pinholes and cracks are easily generated during molding. If a pinhole or crack occurs in the battery packaging material, the electrolyte will penetrate into the barrier layer and form a metal precipitate, which may result in a short circuit. Therefore, it is essential that the film-like battery packaging material has a property that makes it difficult for pinholes and the like to occur during molding, i.e., excellent moldability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2008-287971 A Summary of the Invention [Problem to be solved by the invention]

[0007] In recent years, with the demand for smaller and thinner batteries, there has been a demand for even thinner battery packaging materials. However, when the thickness of the battery packaging material composed of the above-mentioned film-like laminate is extremely thin, for example, 100 μm or less, there is a problem that cracks and pinholes are likely to occur during molding, making it difficult to impart high moldability.

[0008] A primary object of the present invention is to provide a packaging material for batteries that is made of a laminate having at least a base material layer, a barrier layer, and a heat-sealable resin layer in this order, and that has excellent moldability. [Means for solving the problem]

[0009] The present inventors have conducted intensive studies to solve the above problems. As a result, they have found that a battery packaging material consisting of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order has excellent moldability, when the thickness of the laminate is 100 μm or less, and the breaking energy per unit width of 1 m calculated from the curve of "measurement load (N / 15 mm)-displacement amount" measured when a tensile test is performed on the laminate under the following test conditions, the breaking energy X in one direction perpendicular to the thickness direction of the laminate and the breaking energy Y in another direction perpendicular to both the one direction and the thickness direction of the laminate are 200 J or more. The present invention has been completed based on these findings and through further studies. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Gauge distance: 30mm The length of the test piece shall be 100 mm. However, if only a test piece shorter than 100 mm in length can be prepared, the test piece that is as long as possible (as close to 100 mm as possible) shall be measured, provided that the gauge length can be secured and both ends of the test piece can be grasped during measurement.

[0010] That is, the present invention provides a battery packaging material and a battery according to the following aspects. Item 1. The laminate is made of at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The thickness of the laminate is 100 μm or less, The laminate is subjected to a tensile test under the following test conditions, and the breaking energy per unit width of 1 m is calculated from a curve of a measured load (N / 15 mm) versus a displacement amount measured, and the sum X+Y of the breaking energy X in one direction perpendicular to the thickness direction of the laminate and the breaking energy Y in another direction perpendicular to both the one direction and the thickness direction of the laminate is 200 J or more. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Gauge distance: 30mm Item 2. The battery packaging material according to Item 1, wherein the one direction is the MD of the laminate, and the other direction is the TD of the laminate. Item 3. The battery packaging material according to Item 1 or 2, wherein the laminate has a puncture strength of 15 N or more as measured from the base material layer side by a method conforming to the provisions of JIS Z1707:1995. Item 4. The packaging material for batteries according to any one of Items 1 to 3, further comprising an adhesive layer between the base layer and the barrier layer. Item 5. The battery packaging material according to Item 4, wherein the adhesive layer contains a colorant. Item 6. The battery packaging material according to Item 4 or 5, further comprising a colored layer between the base layer and the adhesive layer. Item 7. The packaging material for batteries according to any one of Items 1 to 6, further comprising a surface coating layer on the opposite side of the base material layer to the barrier layer. Item 8. A battery, comprising a battery element including at least a positive electrode, a negative electrode, and an electrolyte, housed in a package formed from the battery packaging material according to any one of Items 1 to 7. Effect of the Invention

[0011] According to the present invention, in a battery packaging material made of a laminate having at least a base material layer, a barrier layer, and a heat-sealable resin layer in this order, although the thickness of the laminate is very thin at 100 μm or less, with respect to the breaking energy per unit width of 1 m calculated from the curve of "measured load (N / 15 mm) - displacement amount" measured when a tensile test is performed on the laminate under the test conditions, the sum X+Y of the breaking energy X in one direction perpendicular to the thickness direction of the laminate and the breaking energy Y in another direction perpendicular to both the one direction and the thickness direction of the laminate is 200 J or more, thereby providing a battery packaging material with excellent formability. [Brief description of the drawings]

[0012] [Figure 1] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 2] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 3] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Figure 4] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Diagram 5] 1 is a diagram showing an example of a cross-sectional structure of a battery packaging material of the present invention. [Figure 6] 1 shows a curve (MD) of measured load (N / 15 mm) versus displacement obtained in a tensile test of the battery packaging material of Example 5. [Figure 7] FIG. 1 is a schematic diagram showing a portion where data on a curve of measured load (N / 15 mm) vs. displacement amount is integrated. [Figure 8] FIG. 2 is a schematic diagram for explaining a method for evaluating curl caused by molding of a battery packaging material. [Figure 9]FIG. 2 is a schematic diagram for explaining a method for evaluating curl caused by molding of a battery packaging material. [Figure 10] FIG. 2 is a schematic diagram of a barrier layer of a test sample after molding in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The battery packaging material of the present invention is composed of a laminate having at least a base layer, a barrier layer, and a heat-sealable resin layer in this order, the thickness of the laminate is 100 μm or less, and the laminate is characterized in that, with respect to the breaking energy per unit width of 1 m calculated from a curve of a measured load (N / 15 mm) vs. a displacement amount measured when a tensile test is performed under the following test conditions, the total X+Y of the breaking energy X in one direction perpendicular to the thickness direction of the laminate and the breaking energy Y in another direction perpendicular to both the one direction and the thickness direction of the laminate is 200 J or more. The battery packaging material of the present invention will be described in detail below. (Test conditions) Test speed: 50mm / min Test piece width: 15mm Gauge distance: 30mm

[0014] In this specification, the numerical range indicated by "to" means "greater than or equal to" or "less than or equal to." For example, the expression "2 to 15 mm" means 2 mm or more and 15 mm or less.

[0015] 1.Layer structure and physical properties of battery packaging materials The battery packaging material of the present invention is composed of a laminate in which at least a base material layer 1, a barrier layer 3, and a heat-sealable resin layer 4 are laminated in this order, as shown in, for example, Figures 1 to 5. In the battery packaging material of the present invention, the base material layer 1 is the outermost layer, and the heat-sealable resin layer 4 is the innermost layer. That is, when the battery is assembled, the heat-sealable resin layers 4 located on the periphery of the battery element are heat-sealed to each other to seal the battery element, thereby sealing the battery element.

[0016] In the battery packaging material of the present invention, as shown in, for example, Figs. 2 to 5, an adhesive layer 2 may be provided between the base material layer 1 and the barrier layer 3, if necessary, in order to enhance the adhesion therebetween. In addition, in the battery packaging material of the present invention, as shown in, for example, Figs. 3 to 5, an adhesive layer 5 may be provided between the barrier layer 3 and the heat-sealable resin layer 4, if necessary, in order to enhance the adhesion therebetween. In addition, as shown in Figs. 4 and 5, a surface coating layer 6 may be provided on the outer side of the base material layer 1 (the side opposite to the heat-sealable resin layer 4), if necessary. In addition, as shown in Fig. 5, a colored layer 7 may be provided between the base material layer 1 and the adhesive layer 2, if necessary.

[0017] The laminate constituting the battery packaging material of the present invention has a thickness of 100 μm or less, and with respect to the breaking energy per unit width 1 m calculated from the curve of "measurement load (N / 15 mm)-displacement amount" measured when a tensile test is performed under the above test conditions, the total X+Y of the breaking energy X in one direction perpendicular to the thickness direction of the laminate (i.e., the lamination direction of the laminate) and the breaking energy Y in the other direction perpendicular to both the one direction and the thickness direction of the laminate (i.e., the other direction is perpendicular to the one direction and also perpendicular to the thickness direction of the laminate) is 200 J or more. From the viewpoint of further improving the moldability while reducing the thickness of the battery packaging material, it is preferable that the one direction is the MD (Machine Direction) of the laminate, and the other direction is the TD (Transverse Direction) of the laminate. That is, regarding the breaking energy per unit width 1 m calculated from the curve of "measurement load (N / 15 mm)-displacement amount" measured when a tensile test is performed under the above test conditions, the sum X+Y of the breaking energy X in MD, which is the flow direction of the laminate, and the breaking energy Y in TD, which is the perpendicular direction, is preferably 200 J or more. In the present invention, the tensile test means a test of tensile properties.

[0018] In addition, from the viewpoint of improving moldability while reducing the thickness of the battery packaging material, the preferable upper limit of the total breaking energy X+Y is about 700 J or less, about 500 J or less, about 495 J or less, about 450 J or less, about 445 J or less, about 400 J or less, less than about 400 J, about and the lower limit is preferably about 250 J or more, more preferably about 300 J or more. The range of the total breaking energy X+Y is preferably about 200 to 700 J, about 200 to 500 J, about 200 to 495 J, about 200 to 450 J, about 200 to 445 J, about 200 to 400 J, about 200 J or more but less than about 400 J, about 200 to 380 J, about 250 to 700 J, about 250 to 500 J, about 250 to 495 J, about 200 to 500 J, about 25 ... Examples include approximately 50 to 450J, approximately 250 to 445J, approximately 250 to 400J, approximately 250J or more but less than approximately 400J, approximately 250 to 380J, approximately 300 to 700J, approximately 300 to 500J, approximately 300 to 495J, approximately 300 to 450J, approximately 300 to 445J, approximately 300 to 400J, approximately 300J or more but less than approximately 400J, and approximately 300 to 380J.

[0019] The method of making the total breaking energy X+Y 200 J or more includes adjusting the materials and thicknesses of the base layer, barrier layer, and heat-fusible resin layer constituting the laminate. The layer that contributes most to the magnitude of the breaking energy is the base layer. The material constituting the base layer is described below, and in the manufacturing process of the base layer, for example, the type of film-forming method and the conditions during film-forming (for example, film-forming temperature, stretching ratio, cooling temperature, cooling rate, heat setting temperature after stretching) are appropriately adjusted. Examples of the film-forming method include the T-die method, the calendar method, and the tubular method. In addition, in order to make the total breaking energy X+Y 200 J or more, it is preferable to heat the laminate at an appropriate temperature and for an appropriate time in the heating process after laminating each layer. By adopting an appropriate temperature and time, it is possible to improve the adhesion of each layer while suppressing damage to the laminate, especially to the base layer. The upper limit of the heating temperature in the heating step is preferably about 185°C or less, more preferably about 180°C or less, and even more preferably 178°C or less, and the lower limit of the heating temperature is preferably 150°C or more, more preferably 160°C or more, and even more preferably 165°C or more. The preferred range of the heating temperature in the heating step is about 150 to 185°C, about 150 to 180°C, about 150 to 178°C, about 160 to 185°C, about 160 to 180°C, about 160 to 178°C, about 165 to 185°C, about 160 to 180°C, and about 160 to 178°C. The upper limit of the heating time in the heating step is preferably 30 minutes or less, more preferably 15 minutes or less, and even more preferably 10 minutes or less, and the lower limit is preferably 0.1 minutes or more, more preferably 0.5 minutes or more, and even more preferably 1 minute or more. It is preferable to combine the heating temperature and heating time in the heating step from among these.

[0020] In the battery packaging material, the MD and TD of the barrier layer described later can usually be distinguished during the manufacturing process. For example, when the barrier layer is made of aluminum foil, linear streaks called rolling marks are formed on the surface of the aluminum foil in the rolling direction (RD) of the aluminum foil. Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum foil can be grasped by observing the surface of the aluminum foil. In addition, in the manufacturing process of the laminate, the MD of the laminate usually coincides with the RD of the aluminum foil, so the MD of the laminate can be identified by observing the surface of the aluminum foil of the laminate and identifying the rolling direction (RD) of the aluminum foil. In addition, since the TD of the laminate is perpendicular to the MD of the laminate, the TD of the laminate can also be identified.

[0021] In the present invention, the breaking energy X, Y per unit width 1 m in the one direction and the other direction of the laminate constituting the battery packaging material is calculated by acquiring data of the measured load (N / 15 mm)-displacement curve measured when performing a tensile test under the test conditions for the one direction and the other direction of the laminate, saving the data in a csv file format, and integrating the data until the laminate breaks using a spreadsheet software (Microsoft Excel (registered trademark)). At this time, the breaking energy per 1 m width of each battery packaging material is converted (divided by 0.015) by the spreadsheet software and calculated. Then, the breaking energy per unit width 1 m in the one direction and the breaking energy X, Y per unit width 1 m in the other direction are summed up. Note that when the laminate breaks means when the test piece breaks. Note that five battery packaging materials are prepared for each measurement target, and the breaking energy of the laminate is determined by, for example, taking the average of the three values ​​excluding the maximum and minimum values ​​of the breaking energy values ​​for the five samples. Even if five samples cannot be prepared, it is preferable to use the average of the number of samples that can be measured. In addition, a commercially available tensile tester can be used for the tensile test.

[0022] From the viewpoint of improving the moldability while reducing the thickness of the battery packaging material, the laminate constituting the battery packaging material of the present invention has a puncture strength measured from the base layer 1 side by a method conforming to the provisions of JIS Z1707:1995, the lower limit of which is preferably about 15N or more, more preferably about 18N or more, and even more preferably about 19N or more, and the upper limit of which is preferably about 30N or less, more preferably about 25N or less, and even more preferably 22N or less. The range of the puncture strength is preferably about 15 to 30N, about 15 to 25N, about 18 to 30N, about 18 to 25N, about 18 to 22N, about 19 to 30N, about 19 to 25N, and about 19 to 22N. From the viewpoint of suppressing curling due to molding of the battery packaging material, the puncture strength is preferably about 22N or less. The method for measuring the puncture strength of the laminate is as follows.

[0023] <Puncture strength of laminate> The puncture strength from the base layer side of the laminate constituting the battery packaging material is measured by a method conforming to the provisions of JIS Z1707:1995. Specifically, in a measurement environment of 23±2°C and relative humidity (50±5)%, a test piece is fixed with a 115mm diameter stand with a 15mm opening in the center and a pressure plate, and a semicircular needle with a diameter of 1.0mm and a tip radius of 0.5mm is pierced at a speed of 50±5mm per minute, and the maximum stress until the needle penetrates is measured. Five test pieces are measured, and their average value is calculated. If there are not enough test pieces to measure five, the number that can be measured is measured, and the average value is calculated.

[0024] The wet tension on the base layer 1 side of the laminate constituting the battery packaging material of the present invention is not particularly limited, but is preferably about 30 to 60 mN / m from the viewpoint of improving moldability while reducing the thickness of the battery packaging material. Methods for adjusting the wet tension include a method of adjusting the amount of lubricant present on the surface on the base layer 1 side, and a method of subjecting the surface on the base layer 1 side to a surface treatment (corona treatment, etc.). The wet tension is measured as follows.

[0025] <Wetting tension measurement> Using a wetting reagent conforming to the JIS standard, the wetting tension of the base layer side of the laminate constituting the battery packaging material is measured. The test method conforms to JIS K6768:1999. Using a mixture for wetting tension testing, the reagent soaked in a cotton swab is applied 6 cm to the surface of the base layer side constituting the battery packaging material. 2 A line of about 100g of the liquid is applied, and the test is judged based on whether the liquid film breaks after 2 seconds. If the liquid film does not break, proceed to the mixed liquid with the next highest surface tension, and if it does break, proceed to the mixed liquid with the next lowest surface tension. Repeat this process to select a mixed liquid that can wet the surface of the test piece in 2 seconds. The wetting tension is measured in an environment of 23°C and 50% relative humidity.

[0026] Furthermore, the battery packaging material of the present invention has a molding depth at which the barrier layer 3 described below has a thickness of 20 μm (i.e., the molding depth at which the barrier layer 3 of the battery packaging material has a thickness of 20 μm when the battery packaging material of the present invention is subjected to molding) of preferably 4.5 mm or more, more preferably 5.0 mm or more, and preferably 10.0 mm or less, more preferably 8.0 mm or less, with preferred ranges being about 4.5 to 10.0 mm, about 4.5 to 8.0 mm, about 5.0 to 10.0 mm, and about 5.0 to 8.0 mm. Specifically, the molding depth is a value measured by the method described in the Examples.

[0027] The limit forming depth of the battery packaging material of the present invention is preferably 4.0 mm or more, more preferably 5.5 mm or more, and is preferably 12.0 mm or less, more preferably 10.0 mm or less, with preferred ranges being about 4.0 to 12.0 mm, about 4.0 to 10.0 mm, about 5.5 to 12.0 mm, and about 5.5 to 10.0 mm. The limit forming depth is specifically a value measured by the method described in the Examples.

[0028] The thickness of the laminate constituting the battery packaging material of the present invention is not particularly limited as long as it is 100 μm or less, but from the viewpoint of making the thickness as thin as possible while ensuring excellent moldability, the upper limit is preferably about 95 μm or less, more preferably about 89 μm or less, and even more preferably about 75 μm or less, and the lower limit is preferably about 35 μm or more, more preferably about 45 μm or more. In addition, the range of the thickness of the laminate is preferably about 35 to 100 μm, about 35 to 95 μm, about 45 to 95 μm, about 35 to 89 μm, about 45 to 89 μm, about 35 to 75 μm, and about 45 to 75 μm. Although the thickness of the laminate constituting the battery packaging material of the present invention is as thin as 100 μm or less, according to the present invention, it can exhibit excellent moldability. Therefore, the battery packaging material of the present invention can contribute to improving the energy density of the battery.

[0029] 2. Layers that form the battery packaging material [Base material layer 1] In the battery packaging material of the present invention, the base layer 1 is a layer located on the outermost layer side. The material forming the base layer 1 is not particularly limited as long as it has insulating properties. Examples of materials forming the base layer 1 include polyester, polyamide, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, polycarbonate, and mixtures and copolymers thereof.

[0030] Specific examples of polyesters include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolymerized polyesters mainly composed of ethylene terephthalate as repeating units, copolymerized polyesters mainly composed of butylene terephthalate as repeating units, etc. Specific examples of copolymerized polyesters mainly composed of ethylene terephthalate as repeating units include copolymer polyesters in which ethylene terephthalate as a main repeating unit is polymerized with ethylene isophthalate (hereinafter abbreviated as polyethylene (terephthalate / isophthalate)), polyethylene (terephthalate / isophthalate), polyethylene (terephthalate / adipate), polyethylene (terephthalate / sodium sulfoisophthalate), polyethylene (terephthalate / sodium isophthalate), polyethylene (terephthalate / phenyl-dicarboxylate), polyethylene (terephthalate / decane dicarboxylate), etc. Specific examples of copolymer polyesters containing butylene terephthalate as the main repeating unit include copolymer polyesters in which butylene terephthalate as the main repeating unit is polymerized with butylene isophthalate (hereinafter abbreviated as polybutylene (terephthalate / isophthalate)), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene naphthalate, etc. These polyesters may be used alone or in combination of two or more. Polyesters have the advantage of being excellent in electrolyte resistance and being less likely to cause whitening or the like due to adhesion of electrolyte, and are therefore suitably used as materials for forming the base layer 1.

[0031] Specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid, and aromatic polyamides such as polymetaxylylene adipamide (MXD6); alicyclic polyamides such as polyaminomethylcyclohexyl adipamide (PACM6); polyamides copolymerized with lactam components and isocyanate components such as 4,4'-diphenylmethane-diisocyanate; polyesteramide copolymers and polyetheresteramide copolymers, which are copolymers of copolymerized polyamides with polyesters or polyalkylene ether glycols; and copolymers thereof. These polyamides may be used alone or in combination of two or more. A stretched polyamide film has excellent stretchability and can prevent whitening due to resin cracking of the base layer 1 during molding, and is therefore preferably used as a material for forming the base layer 1.

[0032] The substrate layer 1 may be formed of a uniaxially or biaxially stretched resin film, or may be formed of an unstretched resin film. Among them, a uniaxially or biaxially stretched resin film, particularly a biaxially stretched resin film, is preferably used as the substrate layer 1 because its heat resistance is improved by oriented crystallization. The substrate layer 1 may be formed by coating the barrier layer 3 with the above-mentioned material.

[0033] Among these, the resin film forming the base layer 1 is preferably nylon or polyester, more preferably biaxially oriented nylon or biaxially oriented polyester, and particularly preferably biaxially oriented nylon.

[0034] In order to improve pinhole resistance and insulation when used as a battery packaging material, the base layer 1 can be laminated (multilayer structure) with at least one of resin films and coatings made of different materials. Specifically, a multilayer structure in which a polyester film and a nylon film are laminated, a multilayer structure in which multiple nylon films are laminated, a multilayer structure in which multiple polyester films are laminated, etc. can be mentioned. When the base layer 1 has a multilayer structure, a laminate of a biaxially oriented nylon film and a biaxially oriented polyester film, a laminate in which multiple biaxially oriented nylon films are laminated, or a laminate in which multiple biaxially oriented polyester films are laminated is preferable, and a specific example is a laminate in which two layers of biaxially oriented nylon film are laminated. In addition, since biaxially oriented polyester is less likely to discolor when an electrolyte solution adheres to the surface, for example, when the base layer 1 has a multilayer structure of a laminate of a biaxially oriented nylon film and a biaxially oriented polyester film, the base layer 1 is preferably a laminate having biaxially oriented nylon and biaxially oriented polyester in this order from the barrier layer 3 side. When the base layer 1 has a multi-layer structure, the thickness of each layer is preferably about 3 to 25 μm.

[0035] When the base material layer 1 has a multi-layer structure, each resin film may be bonded via an adhesive, or may be directly laminated without an adhesive. When bonding without an adhesive, for example, a method of bonding in a thermally molten state such as a co-extrusion method, a sandwich lamination method, or a thermal lamination method may be mentioned. When bonding via an adhesive, the adhesive used may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the bonding mechanism of the adhesive is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, an ultraviolet curing type, an electron beam curing type, and the like. Specific examples of the adhesive include the same adhesives as those exemplified in the adhesive layer 2. The thickness of the adhesive may also be the same as that of the adhesive layer 2.

[0036] In the present invention, from the viewpoint of improving the moldability of the battery packaging material, it is preferable that a lubricant is attached to the surface of the base layer 1. The lubricant is not particularly limited, but is preferably an amide-based lubricant. Specific examples of amide-based lubricants include, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, methylol amides, saturated fatty acid bisamides, and unsaturated fatty acid bisamides. Specific examples of saturated fatty acid amides include lauric acid amides, palmitic acid amides, stearic acid amides, behenic acid amides, and hydroxystearic acid amides. Specific examples of unsaturated fatty acid amides include oleic acid amides and erucic acid amides. Specific examples of substituted amides include N-oleyl palmitic acid amides, N-stearyl stearic acid amides, N-stearyl oleic acid amides, N-oleyl stearic acid amides, and N-stearyl erucic acid amides. Specific examples of methylol amides include methylol stearic acid amides. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, N,N'-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N'-dioleyl adipic acid amide, N,N'-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearamide ethyl stearate, etc. Specific examples of aromatic bisamides include m-xylylene bisstearic acid amide, m-xylylene bishydroxystearic acid amide, N,N'-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more kinds.

[0037] The content of the lubricant in the base layer 1 is not particularly limited, but from the viewpoint of improving the formability and insulating properties of the electronic packaging material, it is preferably about 0.01 to 0.2 mass %, more preferably about 0.05 to 0.15 mass %.

[0038] From the viewpoint of obtaining a battery packaging material with excellent moldability while reducing the thickness of the battery packaging material, the lower limit of the thickness of the base material layer 1 is preferably about 8 μm or more, more preferably about 10 μm or more, and the upper limit is preferably about 25 μm or less, more preferably about 20 μm or less. The thickness of the base material layer 1 is preferably in the range of about 8 to 25 μm, about 8 to 20 μm, about 10 to 25 μm, or about 10 to 20 μm. In the present invention, when the base material layer 1 has a multilayer structure bonded with an adhesive, the thickness of the base material layer 1 does not include the thickness of the adhesive.

[0039] [Adhesive layer 2] In the battery packaging material of the present invention, the adhesive layer 2 is a layer provided between the base material layer 1 and the barrier layer 3 in order to firmly bond them together.

[0040] The adhesive layer 2 is formed of an adhesive capable of bonding the base material layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 may be a two-component curing adhesive or a one-component curing adhesive. Furthermore, the adhesion mechanism of the adhesive used to form the adhesive layer 2 is not particularly limited, and may be any of a chemical reaction type, a solvent volatilization type, a thermal melting type, a thermal pressure type, and the like.

[0041] Specific examples of adhesive components that can be used to form the adhesive layer 2 include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolymerized polyester; polyether-based adhesives; polyurethane-based adhesives; epoxy-based resins; phenol-based resins; polyamide-based resins such as nylon 6, nylon 66, nylon 12, and copolymerized polyamide; polyolefin-based resins such as polyolefin, carboxylic acid-modified polyolefin, and metal-modified polyolefin; polyvinyl acetate-based resins; cellulose-based adhesives; (meth)acrylic resins; polyimide-based resins; polycarbonate; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; and silicone-based resins. These adhesive components may be used alone or in combination of two or more. Among these adhesive components, polyurethane-based adhesives are preferred.

[0042] The adhesive layer 2 may also contain a colorant. When the adhesive layer 2 contains a colorant, the battery packaging material can be colored. As the colorant, known colorants such as pigments and dyes can be used. The colorant may be used alone or in combination of two or more types.

[0043] For example, specific examples of inorganic pigments preferably include carbon black and titanium oxide.Specific examples of organic pigments preferably include azo pigments, phthalocyanine pigments, and condensed polycyclic pigments.Examples of azo pigments include soluble pigments such as Watching Red and Carmine 6C; insoluble azo pigments such as monoazo yellow, disazo yellow, pyrazolone orange, pyrazolone red, and permanent red.Examples of phthalocyanine pigments include copper phthalocyanine pigments and metal-free phthalocyanine pigments such as blue pigments and green pigments.Examples of condensed polycyclic pigments include dioxazine violet and quinacridone violet.Examples of pigments that can be used include pearl pigments and fluorescent pigments.

[0044] Among colorants, carbon black is preferred in order to give the battery packaging material a black appearance, for example.

[0045] The average particle size of the pigment is not particularly limited and may be, for example, about 0.05 to 5 μm, and preferably about 0.08 to 2 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0046] The content of the pigment in the adhesive layer 2 is not particularly limited as long as it colors the battery packaging material, and may be, for example, about 5 to 60 mass %.

[0047] The thickness of the adhesive layer 2 is not particularly limited as long as it functions as an adhesive layer, but may be, for example, about 1 to 10 μm, and preferably about 2 to 5 μm.

[0048] [Colored layer 7] The colored layer 7 is a layer that is provided, if necessary, between the base material layer 1 and the adhesive layer 2. By providing the colored layer 7, the battery packaging material can be colored.

[0049] The colored layer 7 can be formed, for example, by applying an ink containing a colorant to the surface of the base layer 1. As the colorant, known materials such as pigments and dyes can be used. Furthermore, only one type of colorant may be used, or two or more types may be mixed together.

[0050] Specific examples of the colorant contained in the colored layer 7 include the same as those exemplified in the section [Adhesive layer 2].

[0051] The ink for forming the colored layer 7 is not particularly limited, and any known ink can be used. Specific examples of the ink include ink containing a colorant, a diamine, a polyol, and a curing agent. Note that any known solvent can be used as the solvent contained in the ink, and examples of the solvent include toluene.

[0052] The diamine is not particularly limited, and examples thereof include ethylenediamine, dimer diamine, 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, dicyclohexylmethanediamine, 2-hydroxyethylpropylenediamine, etc. Among them, it is preferable to use one or more diamines selected from the group consisting of ethylenediamine, dimer diamine, 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, and dicyclohexylmethanediamine as the diamine.

[0053] Diamines react faster with curing agents (such as isocyanates) than polyols, and can achieve curing in a short time. That is, diamines react with the curing agent together with the polyol to promote crosslinking and curing of the ink.

[0054] The polyol is not particularly limited, but it is preferable to use one or more polyols selected from the group consisting of polyurethane polyols, polyester polyols, and polyether polyols.

[0055] The number average molecular weight of the polyol is preferably in the range of about 1000 to 8000. When it is 1000 or more, the adhesive strength after curing can be increased, and when it is 8000 or less, the reaction rate with the curing agent can be increased.

[0056] The curing agent is not particularly limited, but examples thereof include isocyanate compounds. Examples of isocyanate compounds that can be used include various aromatic, aliphatic, and alicyclic isocyanate compounds. Specific examples include toluene diisocyanate (TDI), diphenylmethane diisocyanate, hexamethylene diisocyanate (HDI), and isophorone diisocyanate.

[0057] In the colored layer 7, the content of the colorant is not particularly limited as long as it can color the battery packaging material, and may be, for example, about 5 to 60 mass %. For example, when the colorant is carbon black, the content of carbon black is preferably about 20 to 50 mass %. The total content of the diamine, polyol, and curing agent is preferably about 40 to 85 mass %. The curing agent is preferably about 2 to 20 parts by mass per 100 parts by mass of the total amount of the colorant, diamine, and polyol.

[0058] The thickness (after drying) of the colored layer 7 is preferably about 1 to 4 μm. When the thickness is 1 μm or more, the color tone of the colored layer 7 does not remain transparent, and the color and gloss of the barrier layer 3 can be sufficiently concealed. Furthermore, when the thickness is 4 μm or less, partial cracking of the colored layer 7 during molding can be sufficiently prevented.

[0059] The colored layer 7 can be formed, for example, by applying an ink for forming the colored layer 7 to the surface of the base material layer 1. Examples of the method for applying the ink include a printing method such as a gravure printing method, a reverse roll coating method, and a lip roll coating method.

[0060] [Barrier layer 3] In the battery packaging material, the barrier layer 3 is a layer that has the function of preventing water vapor, oxygen, light, and the like from penetrating into the battery in addition to improving the strength of the battery packaging material. The barrier layer 3 is preferably a metal layer, that is, a layer formed of a metal. Specific examples of metals constituting the barrier layer 3 include aluminum, stainless steel, and titanium, and aluminum is preferred. The barrier layer 3 can be formed, for example, of a metal foil, a metal vapor deposition film, an inorganic oxide vapor deposition film, a carbon-containing inorganic oxide vapor deposition film, or a film provided with these vapor deposition films, and is preferably formed of a metal foil, and more preferably formed of an aluminum foil or a stainless steel foil.

[0061] When the barrier layer 3 is made of aluminum foil, the aluminum foil is made of an aluminum alloy. From the viewpoint of preventing wrinkles or pinholes from occurring in the barrier layer 3 during the production of the battery packaging material, the barrier layer is more preferably made of soft aluminum foil such as annealed aluminum (JIS H4160:1994 A8021H-O, JIS H4160:1994 A8079H-O, JIS H4000:2014 A8021P-O, JIS H4000:2014 A8079P-O).

[0062] In addition, when the barrier layer 3 is made of stainless steel foil, the stainless steel foil is preferably made of austenitic stainless steel. This results in a battery packaging material with high puncture strength, excellent electrolyte resistance and formability. Specific examples of austenitic stainless steel include SUS304, SUS301, and SUS316L, and among these, SUS304 is particularly preferred. In addition, the stainless steel foil is particularly improved in ductility and formability by cold rolling. Furthermore, by performing heat treatment and annealing after cold rolling, the balance between the flow direction and the width direction is improved, and formability is improved. In addition, in order to stabilize the effect of the chemical conversion treatment described later, it is important to insert a surface cleaning process after rolling or heat treatment. Examples of cleaning methods include cleaning using alkali or acid, and further alkaline electrolytic degreasing cleaning. In addition, ultrasonic treatment, plasma treatment, and the like can also be used in combination. Preferably, alkaline degreasing cleaning or alkaline electrolytic degreasing is preferred. These improve the wettability of the surface, make the chemical conversion treatment uniform, and stabilize the resistance to contents.

[0063] The thickness of the barrier layer 3 is not particularly limited as long as it functions as a barrier layer against water vapor, etc., but is preferably about 50 μm or less, more preferably about 10 to 50 μm, and even more preferably about 10 to 40 μm.

[0064] In addition, it is preferable that at least one surface, preferably both surfaces, of the barrier layer 3 are chemically treated in order to stabilize adhesion and prevent dissolution and corrosion. Here, the chemical conversion treatment refers to a treatment for forming an acid-resistant film on the surface of the barrier layer. Examples of the chemical conversion treatment include chromate treatment using a chromium compound such as chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium biphosphate, chromate acetyl acetate, chromium chloride, and potassium chromium sulfate; phosphate treatment using a phosphate compound such as sodium phosphate, potassium phosphate, ammonium phosphate, and polyphosphoric acid; and chemical conversion treatment using an aminated phenol polymer having repeating units represented by the following general formulas (1) to (4). In the aminated phenol polymer, the repeating units represented by the following general formulas (1) to (4) may be contained alone or in any combination of two or more types.

[0065] [ka]

[0066] [ka]

[0067] [ka]

[0068] [ka]

[0069] In the general formulas (1) to (4), X represents a hydrogen atom, a hydroxy group, an alkyl group, a hydroxyalkyl group, an allyl group, or a benzyl group. 1 and R 2 In the general formulae (1) to (4), X and R each independently represent a hydroxy group, an alkyl group, or a hydroxyalkyl group. 1 and R 2Examples of the alkyl group represented by the formula (I) include linear or branched alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, and a tert-butyl group. 1 and R 2 Examples of the hydroxyalkyl group represented by the formula (1) include linear or branched alkyl groups having 1 to 4 carbon atoms and substituted with one hydroxy group, such as a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, a 1-hydroxypropyl group, a 2-hydroxypropyl group, a 3-hydroxypropyl group, a 1-hydroxybutyl group, a 2-hydroxybutyl group, a 3-hydroxybutyl group, and a 4-hydroxybutyl group. 1 and R 2 The alkyl group and the hydroxyalkyl group represented by the formulas may be the same or different. In the formulas (1) to (4), X is preferably a hydrogen atom, a hydroxy group, or a hydroxyalkyl group. The number average molecular weight of the aminated phenol polymer having the repeating units represented by the formulas (1) to (4) is preferably about 500 to 1,000,000, for example, and more preferably about 1,000 to 20,000.

[0070] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is available in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form a corrosion-resistant layer on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the corrosion-resistant layer. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0071] As a chemical conversion treatment method for imparting corrosion resistance to the barrier layer 3, a method is exemplified in which fine particles of metal oxides such as aluminum oxide, titanium oxide, cerium oxide, and tin oxide, or barium sulfate are dispersed in phosphoric acid, and then baking is performed at 150° C. or higher to form an acid-resistant film on the surface of the barrier layer 3. A resin layer in which a cationic polymer is crosslinked with a crosslinking agent may be further formed on the acid-resistant film. Examples of the cationic polymer include polyethyleneimine, an ionic polymer complex consisting of a polymer having polyethyleneimine and a carboxylic acid, a primary amine-grafted acrylic resin in which a primary amine is graft-polymerized to an acrylic main skeleton, polyallylamine or a derivative thereof, and aminophenol. These cationic polymers may be used alone or in combination of two or more. Examples of the crosslinking agent include a compound having at least one functional group selected from the group consisting of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent. These crosslinking agents may be used alone or in combination of two or more.

[0072] As a specific method for providing an acid-resistant film, for example, at least the inner layer surface of the aluminum foil is first degreased by a known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then a treatment liquid (aqueous solution) mainly composed of a metal phosphate such as a chromium phosphate, a titanium phosphate, a zirconium phosphate, or a zinc phosphate, or a mixture of these metal salts, or a treatment liquid (aqueous solution) mainly composed of a nonmetallic phosphate and a mixture of these nonmetallic salts, or a treatment liquid (aqueous solution) composed of a mixture of these and a water-based synthetic resin such as an acrylic resin, a phenolic resin, or a urethane resin, is applied to the degreased surface by a known coating method such as a roll coating method, a gravure printing method, or a dipping method to form an acid-resistant film. For example, treatment with a chromium phosphate-based treatment solution results in an acid-resistant coating made of chromium phosphate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc., while treatment with a zinc phosphate-based treatment solution results in an acid-resistant coating made of zinc phosphate hydrate, aluminum phosphate, aluminum oxide, aluminum hydroxide, aluminum fluoride, etc.

[0073] As another example of a specific method for providing an acid-resistant coating, for example, at least the inner layer surface of the aluminum foil is first degreased by a well-known treatment method such as an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or an acid activation method, and then the degreased surface is subjected to a well-known anodizing treatment to form an acid-resistant coating.

[0074] Other examples of acid-resistant coatings include phosphate-based and chromate-based coatings. Phosphate-based coatings include zinc phosphate, iron phosphate, manganese phosphate, calcium phosphate, and chromium phosphate, while chromate-based coatings include chromium chromate.

[0075] Other examples of acid-resistant coatings include those made of phosphates, chromates, fluorides, triazine thiol compounds, etc., which prevent delamination between the aluminum and the base layer during embossing, prevent dissolution and corrosion of the aluminum surface, particularly aluminum oxide present on the aluminum surface, caused by hydrogen fluoride produced by a reaction between an electrolyte and water, and improve the adhesion (wettability) of the aluminum surface, preventing delamination between the base layer and aluminum during heat sealing, and in the case of embossed types, preventing delamination between the base layer and aluminum during press molding. Among the substances that form acid-resistant coatings, an aqueous solution composed of three components, phenol resin, chromium (III) fluoride compound, and phosphoric acid, is applied to the aluminum surface and then dried and baked.

[0076] The acid-resistant coating may include a layer having cerium oxide, phosphoric acid or a phosphate, an anionic polymer, and a crosslinking agent that crosslinks the anionic polymer, and the phosphoric acid or the phosphate may be blended in an amount of about 1 to 100 parts by mass per 100 parts by mass of the cerium oxide. It is preferable that the acid-resistant coating has a multilayer structure further including a layer having a cationic polymer and a crosslinking agent that crosslinks the cationic polymer.

[0077] Furthermore, the anionic polymer is preferably poly(meth)acrylic acid or a salt thereof, or a copolymer mainly composed of (meth)acrylic acid or a salt thereof.The crosslinking agent is preferably at least one selected from the group consisting of a compound having any one of a functional group of an isocyanate group, a glycidyl group, a carboxyl group, and an oxazoline group, and a silane coupling agent.

[0078] The phosphoric acid or the phosphate is preferably a condensed phosphoric acid or a condensed phosphate.

[0079] The chemical conversion treatment may be performed using only one type of chemical conversion treatment, or may be performed using a combination of two or more types of chemical conversion treatment. Furthermore, these chemical conversion treatments may be performed using one type of compound alone, or may be performed using a combination of two or more types of compounds. Among the chemical conversion treatments, chromate treatment and chemical conversion treatments combining a chromium compound, a phosphoric acid compound, and an aminated phenol polymer are preferred. Among the chromium compounds, chromate compounds are preferred.

[0080] Specific examples of the acid-resistant coating include those containing at least one of phosphate, chromate, fluoride, and triazine thiol. Also preferred are acid-resistant coatings containing a cerium compound. As the cerium compound, cerium oxide is preferred.

[0081] Specific examples of the acid-resistant film include a phosphate-based film, a chromate-based film, a fluoride-based film, and a triazine thiol compound film. The acid-resistant film may be one of these films, or a combination of a plurality of films. Furthermore, the acid-resistant film may be formed by degreasing the chemically treated surface of the aluminum foil, using a treatment liquid made of a mixture of a metal phosphate and a water-based synthetic resin, or a treatment liquid made of a mixture of a nonmetal phosphate and a water-based synthetic resin.

[0082] The composition of the acid-resistant film can be analyzed, for example, by using time-of-flight secondary ion mass spectrometry. + and Cr + A peak originating from at least one of the above is detected.

[0083] The surface of the aluminum foil is preferably provided with an acid-resistant coating containing at least one element selected from the group consisting of phosphorus, chromium, and cerium. The inclusion of at least one element selected from the group consisting of phosphorus, chromium, and cerium in the acid-resistant coating on the surface of the aluminum foil of the battery packaging material can be confirmed using X-ray photoelectron spectroscopy. Specifically, first, in the battery packaging material, the heat-sealable resin layer, adhesive layer, etc. laminated on the aluminum foil are physically peeled off. Next, the aluminum foil is placed in an electric furnace and organic components present on the surface of the aluminum foil are removed at about 300°C for about 30 minutes. Then, the presence of these elements is confirmed using X-ray photoelectron spectroscopy of the surface of the aluminum foil.

[0084] The amount of the acid-resistant film formed on the surface of the barrier layer 3 in the chemical conversion treatment is not particularly limited. For example, in the case of the above-mentioned chromate treatment, 2 It is desirable that the chromium compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium, the phosphorus compound is contained in an amount of about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus, and the aminated phenol polymer is contained in an amount of about 1.0 to 200 mg, preferably about 5.0 to 150 mg, calculated as phosphorus, per unit area.

[0085] The thickness of the acid-resistant film is not particularly limited, but is preferably about 1 nm to 10 μm, more preferably about 1 to 100 nm, and even more preferably about 1 to 50 nm, from the viewpoint of the cohesive strength of the film and the adhesive strength with the aluminum foil or the heat-fusible resin layer. The thickness of the acid-resistant film can be measured by observation with a transmission electron microscope, or a combination of observation with a transmission electron microscope and energy dispersive X-ray spectroscopy or electron energy loss spectroscopy.

[0086] The chemical conversion treatment is carried out by applying a solution containing a compound used to form an acid-resistant film to the surface of the barrier layer by a bar coating method, a roll coating method, a gravure coating method, a dipping method, or the like, and then heating the barrier layer so that the temperature of the barrier layer is about 70 to 200° C. In addition, before the chemical conversion treatment is carried out on the barrier layer, the barrier layer may be subjected to a degreasing treatment in advance by an alkali dipping method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, or the like. By carrying out the degreasing treatment in this manner, the chemical conversion treatment of the surface of the barrier layer can be carried out more efficiently.

[0087] [Thermal adhesive resin layer 4] In the battery packaging material of the present invention, the heat-sealable resin layer 4 corresponds to the innermost layer, and is a layer that seals the battery element by heat-sealing the heat-sealable resin layers together during assembly of the battery.

[0088] The resin component used in the heat-sealable resin layer 4 is not particularly limited as long as it is heat-sealable, and examples thereof include polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, and carboxylic acid-modified cyclic polyolefin. That is, the resin constituting the heat-sealable resin layer 4 may or may not contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The presence of a polyolefin skeleton in the resin constituting the heat-sealable resin layer 4 can be determined by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, it is found that the maleic anhydride-modified polyolefin has a peak at a wave number of 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0089] Specific examples of the polyolefin include polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); ethylene-butene-propylene terpolymers; etc. Among these polyolefins, polyethylene and polypropylene are preferable.

[0090] The cyclic polyolefin is a copolymer of an olefin and a cyclic monomer, and examples of the olefins constituting the cyclic polyolefin include ethylene, propylene, 4-methyl-1-pentene, butadiene, and isoprene. Examples of the cyclic monomers constituting the cyclic polyolefin include cyclic alkenes such as norbornene; specifically, cyclic dienes such as cyclopentadiene, dicyclopentadiene, cyclohexadiene, and norbornadiene. Styrene is also a constituting monomer. Among these polyolefins, cyclic alkenes are preferred, and norbornene is more preferred.

[0091] The carboxylic acid-modified polyolefin is a polymer modified by block polymerization or graft polymerization of the polyolefin with a carboxylic acid. Examples of the carboxylic acid used for modification include maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride.

[0092] The carboxylic acid-modified cyclic polyolefin is a polymer obtained by copolymerizing a part of the monomers constituting the cyclic polyolefin with an α,β-unsaturated carboxylic acid or its anhydride, or by block-polymerizing or graft-polymerizing an α,β-unsaturated carboxylic acid or its anhydride to the cyclic polyolefin. The cyclic polyolefin to be modified with the carboxylic acid is the same as described above. The carboxylic acid used for the modification is the same as that used for the modification of the carboxylic acid-modified polyolefin.

[0093] Among these resin components, preferred are carboxylic acid-modified polyolefins; more preferred are carboxylic acid-modified polypropylenes.

[0094] The thermally adhesive resin layer 4 may be formed of one type of resin component alone, or may be formed of a blend polymer of two or more types of resin components. Furthermore, the thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers of the same or different resin components.

[0095] The thickness of the heat-fusible resin layer 4 can be appropriately selected, but is typically about 8 to 50 μm, and preferably about 10 to 40 μm.

[0096] The heat-sealable resin layer 4 may contain a lubricant, etc., if necessary. When the heat-sealable resin layer 4 contains a lubricant, the moldability of the battery packaging material can be improved. The lubricant is not particularly limited, and a known lubricant can be used, for example, those exemplified in the above-mentioned base layer 1. The lubricant may be used alone, or two or more types may be used in combination. The content of the lubricant in the heat-sealable resin layer 4 is not particularly limited, and from the viewpoint of improving the moldability and insulating property of the electronic packaging material, it is preferably about 0.01 to 0.20 mass%, more preferably about 0.05 to 0.15 mass%.

[0097] [Adhesive layer 5] In the battery packaging material of the present invention, the adhesive layer 5 is a layer that is provided, if necessary, between the barrier layer 3 and the heat-sealable resin layer 4 in order to firmly bond them together.

[0098] The adhesive layer 5 is formed of a resin capable of bonding the barrier layer 3 and the heat-sealable resin layer 4. The adhesive mechanism, the type of adhesive component, and the like of the adhesive used to form the adhesive layer 5 may be the same as those of the adhesive layer 2. The resin used to form the adhesive layer 5 may also be a polyolefin resin such as polyolefin, cyclic polyolefin, carboxylic acid-modified polyolefin, or carboxylic acid-modified cyclic polyolefin exemplified in the heat-sealable resin layer 4. From the viewpoint of excellent adhesion between the barrier layer 3 and the heat-sealable resin layer 4, carboxylic acid-modified polyolefin is preferred as the polyolefin, and carboxylic acid-modified polypropylene is particularly preferred. That is, the resin constituting the adhesive layer 5 may or may not contain a polyolefin skeleton, and preferably contains a polyolefin skeleton. The resin constituting the adhesive layer 5 may contain a polyolefin skeleton, and can be analyzed by, for example, infrared spectroscopy, gas chromatography mass spectrometry, or the like, and the analysis method is not particularly limited. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, the wavelength of the maleic anhydride-modified polyolefin is 1760 cm. -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected around this peak. However, if the degree of acid modification is low, the peak may be small and not detectable. In that case, analysis can be performed using nuclear magnetic resonance spectroscopy.

[0099] Furthermore, from the viewpoint of obtaining a battery packaging material with excellent moldability while reducing the thickness thereof, it is also preferable that the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent. Preferred examples of the acid-modified polyolefin include the same carboxylic acid-modified polyolefin and carboxylic acid-modified cyclic polyolefin exemplified for the heat-sealable resin layer 4.

[0100] The curing agent is not particularly limited as long as it can cure the acid-modified polyolefin, and examples of the curing agent include epoxy-based curing agents, polyfunctional isocyanate-based curing agents, carbodiimide-based curing agents, and oxazoline-based curing agents.

[0101] The epoxy curing agent is not particularly limited as long as it is a compound having at least one epoxy group. Examples of the epoxy curing agent include epoxy resins such as bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerin polyglycidyl ether, and polyglycerin polyglycidyl ether.

[0102] The polyfunctional isocyanate curing agent is not particularly limited as long as it is a compound having two or more isocyanate groups. Specific examples of polyfunctional isocyanate curing agents include isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymerized or nurated products thereof, mixtures thereof, and copolymers with other polymers.

[0103] The carbodiimide-based curing agent is not particularly limited as long as it is a compound having at least one carbodiimide group (-N=C=N-). As the carbodiimide-based curing agent, a polycarbodiimide compound having at least two carbodiimide groups is preferable.

[0104] The oxazoline-based curing agent is not particularly limited as long as it is a compound having an oxazoline skeleton, and specific examples of the oxazoline-based curing agent include the EPOCROS series manufactured by Nippon Shokubai Co., Ltd.

[0105] From the viewpoint of improving the adhesion between the barrier layer 3 and the thermally adhesive resin layer 4 by the adhesive layer 5, the curing agent may be composed of two or more kinds of compounds.

[0106] The content of the curing agent in the resin composition forming the adhesive layer 5 is preferably in the range of approximately 0.1 to 50 mass%, more preferably in the range of approximately 0.1 to 30 mass%, and even more preferably in the range of approximately 0.1 to 10 mass%.

[0107] The thickness of the adhesive layer 5 is not particularly limited as long as it functions as an adhesive layer, but when the adhesive layer 2 is used, the thickness is preferably about 2 to 10 μm, more preferably about 2 to 5 μm. When the resin exemplified in the thermal adhesive resin layer 4 is used, the thickness is preferably about 2 to 50 μm, more preferably about 10 to 40 μm. When the adhesive layer 5 is a cured product of an acid-modified polyolefin and a curing agent, the thickness is preferably about 30 μm or less, more preferably about 0.1 to 20 μm, and even more preferably about 0.5 to 5 μm. When the adhesive layer 5 is a cured product of a resin composition containing an acid-modified polyolefin and a curing agent, the adhesive layer 5 can be formed by applying the resin composition and curing it by heating or the like.

[0108] [Surface coating layer 6] In the battery packaging material of the present invention, a surface coating layer 6 may be provided on the substrate layer 1 (the side of the substrate layer 1 opposite to the barrier layer 3) as needed for the purpose of improving design, electrolyte resistance, abrasion resistance, formability, etc. The surface coating layer 6 is a layer located on the outermost layer when the battery is assembled.

[0109] The surface coating layer 6 can be formed from a resin composition. Components contained in the resin composition include a resin component, a curing accelerator, and additives (fillers, etc.), as described later.

[0110] The resin component contained in the resin composition preferably contains a thermosetting resin. The thermosetting resin may be any resin that undergoes polymerization when heated to form a polymer network structure and harden. Specific examples of the thermosetting resin include polyvinylidene chloride, polyester resin, epoxy resin, amino resin (melamine resin, benzoguanamine resin, etc.), acrylic resin, urethane resin, phenol resin, unsaturated polyester resin, alkyd resin, etc.

[0111] Among these thermosetting resins, from the viewpoints of shortening the curing time and improving moldability and chemical resistance, preferred are urethane resins and epoxy resins, more preferred are two-component curing urethane resins and two-component curing epoxy resins, and particularly preferred are two-component curing epoxy resins.

[0112] A specific example of the two-component curable urethane resin is a combination of a polyol compound (base) and an isocyanate compound (curing agent), and a specific example of the two-component curable epoxy resin is a combination of an epoxy resin (base) and an acid anhydride, an amine compound, or an amino resin (curing agent). In addition, a polyfunctional urethane (meth)acrylate consisting of a combination of a polyfunctional (meth)acrylate (base) having active hydrogen and a polyisocyanate (curing agent) is also preferred as the two-component curable urethane resin.

[0113] In the two-component curing urethane resin, the polyol compound used as the base agent is not particularly limited, and examples thereof include polyester polyol, polyester polyurethane polyol, polyether polyol, polyether polyurethane polyol, etc. These polyol compounds may be used alone or in combination of two or more.

[0114] In the two-component curing urethane resin, the isocyanate-based compound used as a curing agent is not particularly limited, and examples thereof include polyisocyanate, its adduct, its isocyanurate modified product, its carbodiimide modified product, its allophanate modified product, and its biuret modified product. Specific examples of polyisocyanate include diphenylmethane diisocyanate (MDI), polyphenylmethane diisocyanate (polymeric MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), bis(4-isocyanatocyclohexyl)methane (H12MDI), isophorone diisocyanate (IPDI), 1,5-naphthalene diisocyanate (1,5-NDI), 3,3'-dimethyl-4,4'-diphenylene diisocyanate ( Examples of the isocyanate include aromatic diisocyanates such as tetramethyl diisocyanate (TODI) and xylene diisocyanate (XDI); aliphatic diisocyanates such as tramethylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate and isophorone diisocyanate; alicyclic diisocyanates such as 4,4'-methylenebis(cyclohexyl isocyanate) and isophorone diisocyanate; and polycyclic aromatic diisocyanates such as 1,5-naphthalene diisocyanate (1,5-NDI). Specific examples of the adduct include those obtained by adding trimethylolpropane, glycol, or the like to the above polyisocyanates. These isocyanate compounds may be used alone or in combination of two or more.

[0115] These thermosetting resins may also be crosslinkable elastomers. A crosslinkable elastomer is a thermosetting resin that can impart a soft segment to a cured product. For example, in the case of a two-component curing urethane resin or a two-component curing epoxy resin among the crosslinkable elastomers, the above-mentioned base resin may have a structure that can impart a soft segment. The crosslinkable elastomer can be used as a part of the thermosetting resin used to form the layer that constitutes the surface coating layer 6 in order to provide the layer that constitutes the surface coating layer 6 with the desired hardness.

[0116] These thermosetting resins may be used alone or in combination of two or more. The surface coating layer 6 may be formed of a plurality of layers. When the surface coating layer 6 is formed of a plurality of layers, the thermosetting resins used in each layer may be the same or different, and the type of the thermosetting resin may be appropriately selected according to the functions and physical properties to be provided to each layer. For example, among the layers constituting the surface coating layer 6, a thermosetting resin having a polycyclic aromatic skeleton and / or a heterocyclic skeleton is preferably used for the layer forming the outermost layer (the outermost layer located on the opposite side to the substrate layer 1) from the viewpoint of providing excellent chemical resistance. Specific examples of the thermosetting resin having a polycyclic aromatic skeleton include epoxy resins having a polycyclic aromatic skeleton and urethane resins having a polycyclic aromatic skeleton. Specific examples of the thermosetting resin having a heterocyclic skeleton include amino resins such as melamine resins and benzoguanamine resins. These thermosetting resins having a polycyclic aromatic skeleton and / or a heterocyclic skeleton may be either one-component curing type or two-component curing type.

[0117] More specific examples of epoxy resins having a polycyclic aromatic skeleton include a reaction product of dihydroxynaphthalene with epihalohydrin; a reaction product of a condensate of naphthol with aldehydes (naphthol novolac resin) with epihalohydrin; a reaction product of a condensate of dihydroxynaphthalene with aldehydes with epihalohydrin; a reaction product of a condensate of mono- or dihydroxynaphthalene with xylylene glycols with epihalohydrin; a reaction product of an adduct of mono- or dihydroxynaphthalene with a diene compound with epihalohydrin; and a reaction product of polynaphthols in which naphthols are directly coupled with each other with epihalohydrin.

[0118] More specifically, the urethane resin having a polycyclic aromatic skeleton may be a reaction product of a polyol compound and an isocyanate compound having a polycyclic aromatic skeleton.

[0119] (Cure accelerator) The resin composition forming the surface coating layer 6 may further contain a curing accelerator in addition to the above-mentioned resin components. By making the curing accelerator coexist with the thermosetting resin, the surface coating layer 6 can be cured in a short time without aging under high temperature conditions during production, and a layer having a specific hardness can be formed.

[0120] Here, the term "curing accelerator" refers to a substance that does not form a crosslinked structure by itself but accelerates the crosslinking reaction of a thermosetting resin, and has the effect of accelerating the crosslinking reaction of a thermosetting resin and may also form a crosslinked structure by itself.

[0121] The type of curing accelerator is appropriately selected depending on the thermosetting resin used so as to satisfy the above-mentioned hardness. Examples of the accelerator include amidine compounds, carbodiimide compounds, ketimine compounds, hydrazine compounds, sulfonium salts, benzothiazolium salts, and tertiary amine compounds.

[0122] The amidine compound is not particularly limited, but examples thereof include imidazole compounds, 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), and guanidine compounds. Specific examples of the imidazole compound include 2-methylimidazole, 2-ethylimidazole, 2-undecylimidazole, 2,4-dimethylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 1,2-diethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-benzyl-2-methylimidazole, 2,4-diamino-6-[2'-methylimidazole] 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1)']-ethyl-S-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1)']-ethyl-S-triazine, 2,4-diamino-6-[2'-undecylimidazolyl]-ethyl-S-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1)']-ethyl-S-triazine isocyanuric oxidation adduct, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-aryl-4,5-diphenylimidazole, etc. These amidine compounds may be used alone or in combination of two or more.

[0123] The carbodiimide compound is not particularly limited, and examples thereof include N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide, N-[3-(dimethylamino)propyl]-N'-ethylcarbodiimide methiodide, N-tert-butyl-N'-ethylcarbodiimide, N-cyclohexyl-N'-(2-morpholinoethyl)carbodiimide meso-p-toluenesulfonate, N,N'-di-tert-butylcarbodiimide, N,N'-di-p-tolylcarbodiimide, etc. These carbodiimide compounds may be used alone or in combination of two or more.

[0124] The ketimine compound is not particularly limited as long as it has a ketimine bond (N=C), and examples thereof include ketimine compounds obtained by reacting a ketone with an amine. Specific examples of the ketone include methyl ethyl ketone, methyl isopropyl ketone, methyl tert-butyl ketone, methyl cyclohexyl ketone, diethyl ketone, ethyl propyl ketone, ethyl butyl ketone, dipropyl ketone, dibutyl ketone, and diisobutyl ketone. Specific examples of the amine include aromatic polyamines such as o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, m-xylylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, and diaminodiethyldiphenylmethane; and aliphatic polyamines such as ethylenediamine, propylenediamine, butylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexamethylenediamine, trimethylhexamethylenediamine, 1,2-propanediamine, iminobispropylamine, and methyliminobispropylamine. Specific examples of ketimine compounds include monoamines and polyether-skeleton diamines having an ether bond in the main chain, such as N-aminoethylpiperazine and 3-butoxyisopropylamine; alicyclic polyamines, such as isophoronediamine, 1,3-bisaminomethylcyclohexane, 1-cyclohexylamino-3-aminopropane, and 3-aminomethyl-3,3,5-trimethylcyclohexylamine; norbornane-skeleton diamines; polyamidoamines having amino groups at the molecular terminals of polyamide; 2,5-dimethyl-2,5-hexamethylenediamine, menthenediamine, and 1,4-bis(2-amino-2-methylpropyl)piperazine. These ketimine compounds may be used alone or in combination of two or more.

[0125] The hydrazine compound is not particularly limited, and examples thereof include dipic acid dihydrazide, isophthalic acid dihydrazide, etc. These hydrazine compounds may be used alone or in combination of two or more.

[0126] The sulfonium salt is not particularly limited, and examples thereof include alkylsulfonium salts such as 4-acetophenyldimethylsulfonium hexafluoroantimonate, 4-acetophenyldimethylsulfonium hexafluoroarsenate, dimethyl-4-(benzyloxycarbonyloxy)phenylsulfonium hexafluoroantimonate, dimethyl-4-(benzoyloxy)phenylsulfonium hexafluoroantimonate, and dimethyl-4-(benzoyloxy)phenylsulfonium hexafluoroarsenate; benzyl-4-hydroxyphenylmethylsulfonium hexafluoroantimonate, 4-acetoxyphenylbenzylmethylsulfonium hexafluoroantimonate, benzyl-4-methoxyphenylmethylsulfonium hexafluoroantimonate, benzyl-3-chloro-4-hydroxyphenylmethylsulfonium hexafluoroarsenate, and 4-methoxybenzyl-4-hydroxyphenylmethylsulfonium hexafluoroarsenate. benzylsulfonium salts such as dibenzyl-4-hydroxyphenylsulfonium hexafluoroantimonate, dibenzyl-4-hydroxyphenylsulfonium hexafluorophosphate, dibenzyl-4-methoxyphenylsulfonium hexafluoroantimonate, benzyl-4-methoxybenzyl-4-hydroxyphenylsulfonium hexafluorophosphate, and the like; p-chlorobenzyl-4-hydroxyphenylmethylsulfonium hexafluoroantimonate, p-nitrobenzyl-4-hydroxyphenylmethylsulfonium hexafluoroantimonate, 3,5-dichlorobenzyl-4-hydroxyphenylmethylsulfonium hexafluoroantimonate, o-chlorobenzyl-3-chloro-4-hydroxyphenylmethylsulfonium hexafluoroantimonate, and the like. These sulfonium salts may be used alone or in combination of two or more.

[0127] The benzothiazolium salt is not particularly limited, and examples thereof include benzylbenzothiazolium salts such as 3-benzylbenzothiazolium hexafluoroantimonate, 3-benzylbenzothiazolium hexafluorophosphate, 3-benzylbenzothiazolium tetrafluoroborate, 3-(p-methoxybenzyl)benzothiazolium hexafluoroantimonate, 3-benzyl-2-methylthiobenzothiazolium hexafluoroantimonate, and 3-benzyl-5-chlorobenzothiazolium hexafluoroantimonate. These benzothiazolium salts may be used alone or in combination of two or more.

[0128] The tertiary amine compound is not particularly limited, but examples thereof include aliphatic tertiary amines such as trimethylamine, triethylamine, tripropylamine, tributylamine, triethylenediamine, 1,4-diazabicyclo[2.2.2]octane, quinuclidine, and 3-quinuclidinol; aromatic tertiary amines such as dimethylaniline; and heterocyclic tertiary amines such as isoquinoline, pyridine, collidine, and beta-picoline. These tertiary amine compounds may be used alone or in combination of two or more.

[0129] A suitable example of the curing accelerator is one that functions as a thermal acid generator. A thermal acid generator is a substance that generates an acid by heating and functions as a curing accelerator. Among the above-mentioned curing accelerators, specific examples that can function as a thermal acid generator include sulfonium salts and benzothiazolium salts.

[0130] Another suitable example of the curing accelerator is one having thermal latency that is activated under a specific heating condition (e.g., 80 to 200°C, preferably 100 to 160°C) to accelerate the crosslinking reaction of the thermosetting resin. Specific examples of the thermally latent substance among the above-mentioned curing accelerators include epoxy adducts in which an epoxy compound is added to an amidine compound, a hydrazine compound, a tertiary amine compound, or the like.

[0131] Further, another suitable example of the curing accelerator is one having hydrolysis latency, which does not function as a curing agent in a sealed state, i.e., in a moisture-proof state, but functions as a curing agent by hydrolysis under conditions in which the sealed state is opened and moisture is present. Specific examples of the hydrolysis latency among the curing accelerators described above include epoxy adducts in which an epoxy compound is added to an amidine compound, a hydrazine compound, a tertiary amine compound, etc.

[0132] These curing accelerators may be used alone or in combination of two or more. Among these curing accelerators, preferred are amidine compounds and sulfonium salts, and more preferred are amidine compounds.

[0133] These curing accelerators may be used alone or in combination of two or more in the surface coating layer 6. When the surface coating layer 6 is formed of a plurality of layers, the curing accelerators used in the respective layers constituting the surface coating layer 6 may be the same or different, and the type of the curing accelerator may be appropriately selected depending on the functions and physical properties to be provided to each layer.

[0134] When a curing accelerator is used, the content of the curing accelerator in the resin composition used to form the surface coating layer 6 is appropriately set depending on the type of thermosetting resin used, the type of curing accelerator, etc., and for example, the total amount of the curing accelerator per 100 parts by mass of the thermosetting resin is about 0.01 to 6 parts by mass, preferably about 0.05 to 5 parts by mass, and more preferably about 0.1 to 2 parts by mass.

[0135] The surface coating layer 6 preferably contains a filler as an additive. That is, the surface coating layer 6 is preferably formed from a resin composition containing a filler. When the surface coating layer 6 contains a filler, an uneven shape can be formed on the surface of the surface coating layer 6, and a matte feel can be imparted to the battery packaging material. Specific examples of the filler include inorganic fillers such as titanium oxide, silica, talc, clay, heavy calcium carbonate, light calcium carbonate, barium sulfate, calcium silicate, synthetic silicate, aluminum hydroxide, and silicate fine powder. Only one type of filler may be used, or two or more types may be mixed and used.

[0136] Among inorganic fillers, inorganic fillers made of silica or precipitated barium sulfate are preferred because they are easy to handle and obtain. Note that precipitated barium sulfate refers to barium sulfate produced by utilizing a chemical reaction, and is characterized by the ability to control the particle size.

[0137] The content of the filler in the surface coating layer 6 is preferably about 2.0 to 8.7% by mass when the filler is silica having an average particle size of about 1.0 to 3.0 μm, and is preferably about 13.0 to 40.0% by mass when the filler is precipitated barium sulfate having an average particle size of less than 1.5 μm. The filler content is the content of the filler in the surface coating layer 6, and is the content after the solvent has evaporated from the above-mentioned resin composition for forming the surface coating layer 6 containing the filler. The average particle size of the filler is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0138] The surface coating layer 6 may contain at least one of a pigment and a dye as an additive. When the surface coating layer 6 contains at least one of a pigment and a dye, whitening during molding can be more effectively suppressed, and abrasion resistance can also be improved. In addition, when the surface coating layer 6 contains at least one of a pigment and a dye, it is possible to impart distinctiveness to the battery packaging material of the present invention (coloring by at least one of a pigment and a dye), impart a matte design to the surface of the battery packaging material of the present invention, and further increase the thermal conductivity of the battery packaging material of the present invention to improve heat dissipation.

[0139] The material of the pigment is not particularly limited, and may be either an inorganic pigment or an organic pigment. Specific examples of the inorganic pigment include carbon black, carbon nanotubes, graphite, kaolin, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, cerium oxide, calcium sulfate, lithium carbonate, gold, aluminum, copper, and nickel. Specific examples of the organic pigment include azo pigments, polycyclic pigments, lake pigments, and fluorescent pigments. These pigments may be used alone or in combination of two or more.

[0140] The shape of the pigment is not particularly limited, and examples thereof include spherical, fibrous, plate-like, amorphous, balloon-like, etc. The average particle size of the pigment is not particularly limited, and examples thereof include preferably about 0.01 to 3 μm, and more preferably about 0.05 to 1 μm. The average particle size of the pigment is the median size measured by a laser diffraction / scattering type particle size distribution measuring device.

[0141] If necessary, the pigment may be subjected to various surface treatments such as an insulation treatment or a high-dispersion treatment (resin coating treatment).

[0142] The type of dye is not particularly limited as long as it can be dissolved or dispersed in the resin composition used to form the surface coating layer 6, and examples thereof include nitro dyes, azo dyes, stilbene dyes, carbonium dyes, quinoline dyes, methine dyes, thiazole dyes, quinine imine dyes, anthraquinone dyes, indigoid dyes, and phthalocyanine dyes, with azo dyes, carbonium dyes, anthraquinone dyes, and the like being preferred. These dyes may be used alone or in combination of two or more.

[0143] Among these pigments and dyes, from the viewpoint of further improving the heat dissipation properties of the battery packaging material of the present invention, preferred are pigments, more preferred are inorganic pigments, even more preferred are carbon materials such as carbon black, carbon nanotubes, and graphite, and particularly preferred is carbon black.

[0144] When the surface coating layer 6 has a multilayer structure composed of two or more layers, the pigment and / or dye may be contained in any one of the two or more layers, or may be contained in two or more layers. From the viewpoint of reducing the difference in color tone between the molded part and the unmolded part after molding of the battery packaging material of the present invention, it is preferable to have the surface coating layer 6 have a multilayer structure composed of two or more layers and to contain the pigment and / or dye in two or more layers, and it is even more preferable to have the surface coating layer 6 have a three-layer structure composed of three layers and to contain the pigment and / or dye in all three layers.

[0145] When the pigment and / or dye is contained in at least one layer constituting the surface coating layer 6, the content of the pigment and / or dye may be appropriately set according to the type of the pigment and / or dye used, the distinguishability and heat dissipation property to be imparted to the battery packaging material of the present invention, etc. For example, the total amount of the pigment and / or dye may be about 1 to 30 parts by mass relative to 100 parts by mass of the resin component contained in the layer containing the pigment and / or dye. From the viewpoint of imparting even better distinguishability, the total amount of the pigment and / or dye may be about 3 to 20 parts by mass relative to 100 parts by mass of the resin component contained in the layer containing the pigment and / or dye. In addition, from the viewpoint of suppressing the deterioration of moldability caused by the pigment and / or dye as well as the better distinguishability, the total amount of the pigment and / or dye may be about 5 to 15 parts by mass relative to 100 parts by mass of the resin component contained in the layer containing the pigment and / or dye.

[0146] The resin composition used to form the surface coating layer 6 may contain, in addition to the additives described above, other additives such as organic fillers, lubricants, solvents, elastomer resins, etc., as necessary, depending on the functionality that the surface coating layer 6 should have.

[0147] By incorporating an organic filler or a lubricant as an additive into the surface coating layer 6, a slip effect can be imparted to the surface of the battery packaging material of the present invention, thereby improving the formability and processability in press molding and embossing, and improving operability.

[0148] The type of organic filler is not particularly limited, but examples thereof include high melting point nylon, acrylate resin, cross-linked acrylic, cross-linked styrene, cross-linked polyethylene, benzoguanamine, etc. The shape of the organic filler is also not particularly limited, but examples thereof include spherical, fibrous, plate-like, amorphous, balloon-like, etc.

[0149] The lubricant is not particularly limited, and may be, for example, a non-reactive lubricant or a reactive lubricant. In particular, reactive lubricants have the advantage that the lubricant is less likely to bleed out and be lost from the outermost layer constituting the surface coating layer 6, and that it is possible to suppress the occurrence of powdering or offset during use and the decrease in slip effect over time, and therefore, among lubricants, reactive lubricants are preferable.

[0150] Here, the non-reactive lubricant is, for example, a compound that does not have a functional group that reacts with the above-mentioned resin component to chemically bond therewith and can impart slip properties (sliding properties), whereas the reactive lubricant is a compound that has a functional group that reacts with the above-mentioned resin component to chemically bond therewith and can impart slip properties (sliding properties).

[0151] Specific examples of non-reactive lubricants include amide-based lubricants, fatty acid amides, metal soaps, hydrophilic silicones, silicone-grafted acrylics, silicone-grafted epoxies, silicone-grafted polyethers, silicone-grafted polyesters, block-type silicone-acrylic copolymers, polyglycerol-modified silicones, and paraffins. Examples of amide-based lubricants that can be used include the amide-based lubricants described above. These non-reactive lubricants may be used alone or in combination of two or more.

[0152] In addition, in the reactive lubricant, the type of functional group is appropriately set depending on the type of resin component used, and examples thereof include a hydroxyl group, a mercapto group, a hydrolyzable silyl group, an isocyanate group, an epoxy group, a polymerizable vinyl group, a (meth)acryloyl group, etc. In the reactive lubricant, the number of functional groups per molecule is not particularly limited, and examples thereof include 1 to 3, and preferably 1 or 2.

[0153] Specific examples of reactive lubricants include modified silicone having the functional group; modified fluororesin having the functional group; compounds in which the functional group is introduced to fatty acid amides such as stearic acid amide, oleic acid amide, erucic acid amide, and ethylene bisstearic acid amide; metal soaps having the functional group; and paraffins having the functional group. These reactive lubricants may be used alone or in combination of two or more. Among these reactive lubricants, preferred are modified silicone having the functional group, modified fluororesin having the functional group, and silicone modified resin having the functional group. Specific examples of modified silicone include modified silicone having a polymer having the functional group as block polymerized, such as modified silicone having an acrylic resin block polymerized; modified silicone having a monomer having the functional group as graft polymerized, such as modified silicone having an acrylate graft polymerized. In addition, specific examples of the modified fluororesin include modified fluororesins in which a monomer having the functional group is graft-polymerized, such as fluororesins in which acrylate is graft-polymerized; and fluororesins in which a polymer having the functional group is block-polymerized, such as modified fluororesins in which acrylic resin is block-polymerized. In addition, specific examples of the silicone-modified resin include silicone-modified resins in which the functional group is graft-polymerized and silicone is graft-polymerized, such as silicone-modified acrylic resins in which silicone is graft-polymerized to the acrylic resin having the functional group. Among these, particularly preferred reactive lubricants include modified silicones in which a monomer or polymer having the functional group is polymerized at one end of silicone; and modified fluororesins in which a monomer or polymer having the functional group is polymerized at one end of fluororesin. As such modified silicones and modified fluororesins, for example, "Modiper (registered trademark) F / FS series" (manufactured by NOF Corporation) and "Simac (registered trademark) series" (manufactured by Toagosei Co., Ltd.) are commercially available, and these commercially available products can also be used.

[0154] When a lubricant is contained in the resin composition used to form the layer that forms the outermost layer in the surface coating layer 6, the content thereof is not particularly limited, but for example, the total amount of the lubricant per 100 parts by mass of the resin component is about 1 to 12 parts by mass, preferably about 3 to 10 parts by mass, and more preferably about 5 to 8 parts by mass.

[0155] Other specific examples of additives include montmorillonite, synthetic mica, hydrotalcite, zeolite, calcium benzoate, calcium oxalate, magnesium stearate, gold, aluminum, copper, and nickel.

[0156] The method for forming the surface coating layer 6 is not particularly limited, and may be, for example, a method in which a resin composition for forming the surface coating layer 6 is applied onto one surface of the base material layer 1. When an additive is added, the additive may be added to the resin composition, mixed, and then applied.

[0157] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 exhibits the above-mentioned functions, and may be, for example, about 0.5 to 10 μm, and preferably about 1 to 5 μm.

[0158] 3. Manufacturing method of battery packaging material The manufacturing method of the battery packaging material of the present invention is not particularly limited as long as a laminate in which each layer of a predetermined composition is laminated can be obtained. An example of the manufacturing method of the battery packaging material of the present invention is as follows. First, a laminate in which a base layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in order (hereinafter, sometimes referred to as "laminate A") is formed. Specifically, the formation of the laminate A can be performed by a dry lamination method in which an adhesive used for forming the adhesive layer 2 is applied and dried on the base layer 1 or on the barrier layer 3 whose surface has been chemically treated as necessary, by a coating method such as gravure coating or roll coating, and then the barrier layer 3 or the base layer 1 is laminated and the adhesive layer 2 is cured. At this time, aging may be performed as necessary. When a colored layer 7 is provided between the base layer 1 and the adhesive layer 2, an ink for forming the colored layer 7 is applied to the surface on one side of the base layer 1 in advance, and the adhesive layer 2 and the barrier layer 3 are laminated to obtain the laminate A.

[0159] Next, a heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is directly laminated on the barrier layer 3, the resin component constituting the heat-fusible resin layer 4 may be applied on the barrier layer 3 of the laminate A by a method such as gravure coating or roll coating. In addition, in the case of providing the adhesive layer 5 between the barrier layer 3 and the heat-sealable resin layer 4, for example, there can be mentioned (1) a method of laminating the adhesive layer 5 and the heat-sealable resin layer 4 on the barrier layer 3 of the laminate A by co-extruding them (co-extrusion lamination method), (2) a method of separately forming a laminate in which the adhesive layer 5 and the heat-sealable resin layer 4 are laminated, and laminating this on the barrier layer 3 of the laminate A by a thermal lamination method, (3) a method of laminating an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A by an extrusion method or a solution coating, drying at a high temperature, and further baking, and laminating the heat-sealable resin layer 4, which has been formed into a sheet-like film, on this adhesive layer 5 by a thermal lamination method, and (4) a method of laminating the laminate A and the heat-sealable resin layer 4 via the adhesive layer 5 while pouring a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-sealable resin layer 4, which has been formed into a sheet-like film, (sandwich lamination method), and the like.

[0160] When the surface coating layer 6 is provided, the surface coating layer 6 is laminated on the surface of the base layer 1 opposite to the barrier layer 3. The surface coating layer 6 can be formed, for example, by applying the above-mentioned resin for forming the surface coating layer 6 to the surface of the base layer 1. The order of the step of laminating the barrier layer 3 on the surface of the base layer 1 and the step of laminating the surface coating layer 6 on the surface of the base layer 1 is not particularly limited. For example, after forming the surface coating layer 6 on the surface of the base layer 1, the barrier layer 3 may be formed on the surface of the base layer 1 opposite to the surface coating layer 6.

[0161] As described above, a laminate is formed which is composed of the optional surface coating layer 6 / substrate layer 1 / optional adhesive layer 2 / optional barrier layer 3 whose surface is chemically treated / optional adhesive layer 5 / thermally adhesive resin layer 4, and in order to strengthen the adhesiveness of the adhesive layer 2 or adhesive layer 5, the laminate may be subjected to a heat treatment such as a hot roll contact type, hot air type, near infrared type or far infrared type. Conditions for such heat treatment include, for example, about 150 to 250° C. for about 1 to 5 minutes.

[0162] In the battery packaging material of the present invention, each layer constituting the laminate may be subjected to a surface activation treatment such as corona treatment, blast treatment, oxidation treatment, ozone treatment, etc., as necessary, in order to improve or stabilize the film-forming properties, lamination processing, suitability for secondary processing of the final product (pouching, embossing), etc.

[0163] 4. Applications of battery packaging materials The battery packaging material of the present invention is used for a package for hermetically housing battery elements such as a positive electrode, a negative electrode, an electrolyte, etc. That is, a battery element including at least a positive electrode, a negative electrode, and an electrolyte can be housed in a package formed from the battery packaging material of the present invention to form a battery.

[0164] Specifically, a battery element including at least a positive electrode, a negative electrode, and an electrolyte is covered with the battery packaging material of the present invention in such a manner that a flange portion (a region where the heat-sealable resin layers contact each other) can be formed on the periphery of the battery element with the metal terminals connected to each of the positive electrode and the negative electrode protruding outward, and the heat-sealable resin layers of the flange portion are heat-sealed to provide a battery using the battery packaging material. When a battery element is housed in a package formed from the battery packaging material of the present invention, the package is formed so that the heat-sealable resin portion of the battery packaging material of the present invention is on the inside (the surface in contact with the battery element).

[0165] The battery packaging material of the present invention may be used for either primary or secondary batteries, but is preferably used for secondary batteries. The type of secondary battery to which the battery packaging material of the present invention is applied is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries are suitable applications of the battery packaging material of the present invention. EXAMPLES

[0166] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0167] <Production of battery packaging materials> The battery packaging materials of Examples 1 to 5 and Comparative Examples 1 to 3 were manufactured by the following procedure. The layered structure of each battery packaging material is shown in Table 1. In Table 1, SF means a surface coating layer, ON means a biaxially oriented nylon film, DL means an adhesive layer or an adhesive layer formed by a dry lamination method, AL means an aluminum foil, PPa means maleic anhydride-modified polypropylene, PP means random polypropylene, and CPP means an unstretched polypropylene film. The numerical value added after each layer means the thickness of the layer, for example, "ON15" means "a biaxially oriented nylon film having a thickness of 15 μm."

[0168] Example 1 A barrier layer made of aluminum foil (thickness 35 μm, JIS H4160:1994 A8021H-O) with chemical conversion treatment applied on both sides was laminated by dry lamination on a biaxially oriented nylon film (thickness 15 μm) as a substrate layer. Specifically, a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer were laminated to produce a substrate layer / adhesive layer / barrier layer laminate. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed by applying a treatment solution consisting of a phenolic resin, a chromium fluoride compound, and phosphoric acid in an amount of 10 mg / m2 of chromium applied. 2 (dry weight) was applied to both sides of an aluminum foil by roll coating, and then baked.

[0169] Next, a maleic anhydride-modified polypropylene (thickness 20 μm, placed on the barrier layer side) and a random polypropylene (thickness 15 μm, innermost layer) were co-extruded on the barrier layer of the obtained laminate, thereby laminating an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated at 175° C. for 2 minutes to obtain a battery packaging material in which a base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order.

[0170] Example 2 A laminate of a base layer / adhesive layer / barrier layer was produced in the same manner as in Example 1. Next, a solution (2 μm thick after curing) containing maleic anhydride-modified polypropylene and a curing agent (epoxy type) was applied onto the barrier layer of the obtained laminate, and an unstretched polypropylene film (30 μm thick) was further laminated thereon to obtain a battery packaging material in which the base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order.

[0171] Example 3 A barrier layer made of aluminum foil (thickness 35 μm, JIS H4160:1994 A8021H-O) with chemical conversion treatment on both sides was laminated on a biaxially oriented nylon film (thickness 15 μm) as a substrate layer by dry lamination. Specifically, a two-liquid type urethane adhesive (polyol compound and aromatic isocyanate compound) containing carbon black (median diameter 0.191 μm) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer were laminated, and then aging treatment was performed to produce a substrate layer / adhesive layer (black) / barrier layer laminate. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed in the same manner as in Example 1. The average particle size of the carbon black is the median size measured with a laser diffraction / scattering type particle size distribution measuring device ("LA-950" manufactured by Horiba, Ltd.).

[0172] Next, on the barrier layer of the obtained laminate, maleic anhydride-modified polypropylene (thickness 20 μm, arranged on the barrier layer side) and random polypropylene (thickness 15 μm, innermost layer) were co-extruded to laminate an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated at 175° C. for 2 minutes to obtain a laminate in which a base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order. Next, a resin composition containing precipitated barium sulfate having an average particle diameter of 1 μm as a filler, erucic acid amide, and an acrylate resin having an average particle diameter of 2 μm was coated by gravure coating on the surface of the base layer of the obtained laminate so that the thickness after drying was about 3 μm to form a surface coating layer. Next, the obtained laminate was heated to obtain a battery packaging material in which a surface coating layer / base layer / adhesive layer (black) / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order. The average particle size of the precipitated barium sulfate is a median size measured by a laser diffraction / scattering type particle size distribution measuring device ("LA-950" manufactured by Horiba, Ltd.).

[0173] Example 4 A black pigment was printed to a thickness of 1 μm on one surface of a biaxially oriented nylon film (thickness 15 μm) as a base layer to form a black colored layer. Next, a barrier layer made of aluminum foil (thickness 35 μm, JIS H4160:1994 A8021H-O) with chemical conversion treatment on both sides was laminated on the colored layer side of the base layer by a dry lamination method. Specifically, a two-liquid urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the colored layer side of the base layer were laminated, and then aging treatment was performed to produce a laminate of base layer / colored layer (black) / adhesive layer / barrier layer. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed in the same manner as in Example 1.

[0174] Next, a two-liquid urethane adhesive (a polyol compound and an aromatic isocyanate compound) was applied onto the barrier layer of the obtained laminate, forming an adhesive layer (3 μm thick) on the barrier layer. Furthermore, an unstretched polypropylene film (30 μm thick) was laminated onto the adhesive layer. Next, the obtained laminate was heated and subjected to an aging treatment. Next, a resin composition containing a filler was coated onto the surface of the base layer of the obtained laminate to a thickness of 3 μm, forming a surface coating layer. Next, the obtained laminate was heated and aged to obtain a battery packaging material in which a surface coating layer / base layer / colored layer (black) / adhesive layer / barrier layer / adhesive layer / thermally adhesive resin layer were laminated in this order.

[0175] Example 5 A barrier layer made of aluminum foil (thickness 30 μm, JIS H4160:1994 A8021H-O) with chemical conversion treatment applied on both sides was laminated on a biaxially oriented nylon film (thickness 15 μm) as a substrate layer by dry lamination. Specifically, a two-liquid urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer were laminated to prepare a substrate layer / adhesive layer / barrier layer laminate. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed in the same manner as in Example 1.

[0176] Next, a maleic anhydride-modified polypropylene (thickness 14 μm, placed on the barrier layer side) and a random polypropylene (thickness 10 μm, innermost layer) were co-extruded on the barrier layer of the obtained laminate, thereby laminating an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated at 175° C. for 2 minutes to obtain a battery packaging material in which a base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order.

[0177] The wet tension of the surface on the base layer side of the laminate constituting the battery packaging material obtained in each Example was in the range of 30 to 60 mN / m. The wet tension was measured by the following method.

[0178] <Method of measuring wetting tension> Using a wetting reagent conforming to the JIS standard, the wetting tension of the base layer side of the laminate constituting the battery packaging material was measured. The test method conformed to JIS K6768:1999. Using a mixture for wetting tension testing manufactured by Nacalai Tesque, Inc., the reagent soaked in a cotton swab was applied 6 cm to the surface of the base layer side constituting the battery packaging material. 2 A line of about 100 ml of the liquid was applied, and a judgment was made as to whether the liquid film broke after 2 seconds. If the liquid film did not break, the test proceeded to the mixed liquid with the next highest surface tension, and if it did break, the test proceeded to the mixed liquid with the next lowest surface tension. This procedure was repeated to select a mixed liquid that could wet the surface of the test piece in 2 seconds. The wetting tension was measured in an environment of 23°C and 50% relative humidity.

[0179] Comparative Example 1 A barrier layer made of aluminum foil (thickness 25 μm, JIS H4160:1994 A8021H-O) with chemical conversion treatment applied on both sides was laminated on a polyethylene terephthalate film (thickness 12 μm) as a substrate layer by dry lamination. Specifically, a two-liquid urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the barrier layer to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer were laminated to prepare a substrate layer / adhesive layer / barrier layer laminate. The chemical conversion treatment of the aluminum foil used as the barrier layer was performed in the same manner as in Example 1.

[0180] Next, a maleic anhydride-modified polypropylene (thickness 14 μm, placed on the barrier layer side) and a random polypropylene (thickness 10 μm, innermost layer) were co-extruded on the barrier layer of the obtained laminate, thereby laminating an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated at 175° C. for 2 minutes to obtain a battery packaging material in which a base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order.

[0181] Comparative Example 2 A laminate of a base layer / adhesive layer / barrier layer was produced in the same manner as in Comparative Example 1. Next, a solution (2 μm thick after curing) containing maleic anhydride-modified polypropylene and a curing agent (epoxy type) was applied onto the barrier layer of the obtained laminate, and an unstretched polypropylene film (25 μm thick) was further laminated thereon to obtain a battery packaging material in which the base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order.

[0182] Comparative Example 3 A laminate of a base layer / adhesive layer / barrier layer was produced in the same manner as in Example 1. The chemical conversion treatment of the aluminum foil used as the barrier layer was carried out in the same manner as in Example 1. Next, on the barrier layer of the obtained laminate, maleic anhydride-modified polypropylene (thickness 20 μm, arranged on the barrier layer side) and random polypropylene (thickness 15 μm, innermost layer) were co-extruded to laminate an adhesive layer / thermal adhesive resin layer on the barrier layer. Next, the obtained laminate was heated at 190° C. for 2 minutes to obtain a battery packaging material in which the base layer / adhesive layer / barrier layer / adhesive layer / thermal adhesive resin layer were laminated in this order. [Table 1]

[0183] <Measurement of thickness of laminate> The thickness of the laminate constituting each of the battery packaging materials obtained above was measured using a micrometer (Digimatic Micrometer manufactured by Mitutoyo Corporation). The results are shown in Table 2.

[0184] <Break energy of laminate> For each battery packaging material obtained above, the breaking energy per unit width 1 m in MD and TD was calculated by obtaining data on the "measurement load (N / 15 mm)-displacement curve" measured when performing a tensile test under the following test conditions for the MD and TD of each battery packaging material, saving the data in a csv file format, and integrating the data until the laminate breaks using a spreadsheet software (Microsoft Excel (registered trademark)). At this time, the breaking energy per 1 m width of each battery packaging material was converted (divided by 0.015) using the spreadsheet software and calculated. Then, the breaking energy per unit width 1 m in MD and the breaking energy per unit width 1 m in TD were summed up. Five battery packaging materials were prepared for each measurement, and the average of the three breaking energy values ​​for the five samples, excluding the maximum and minimum values, was taken as the breaking energy of the laminate. The results are shown in Table 2. (Test conditions) Tensile testing machine: Shimadzu Corporation product name AGS-XPlus Test speed: 50mm / min Specimen width: 15mm Specimen length: 100mm ·Gage distance: 30mm

[0185] For reference, Fig. 6 shows a curve of the measured load (N / 15 mm) vs. displacement obtained in the tensile test (MD) of the battery packaging material of Example 5. The integral of the data of the measured load (N / 15 mm) vs. displacement curve is the integral value from the start of the tensile test (displacement 0) to the breaking point P of the laminate, as shown in the schematic diagram of Fig. 7, for example, and corresponds to the area of ​​the shaded portion in Fig. 7.

[0186] <Puncture strength of laminate> The puncture strength of each battery packaging material obtained above was measured from the substrate layer side by a method conforming to the provisions of JIS Z1707:1995. Specifically, in a measurement environment of 23±2°C and relative humidity (50±5)%, a test piece was fixed with a 115mm diameter table with a 15mm opening in the center and a presser plate, and a semicircular needle with a diameter of 1.0mm and a tip radius of 0.5mm was pierced at a speed of 50±5mm per minute, and the maximum stress until the needle penetrated was measured. The number of test pieces was five, and the average value was calculated. The puncture strength was measured using Imada's ZTS-500N (force gauge) and MX-500N (measurement stand). The results are shown in Table 2.

[0187] <Evaluation of moldability> Each battery packaging material was cut into a rectangle with a length (MD) of 90 mm and a width (TD) of 150 mm to prepare a test sample. The sample was cold-formed (one-stage drawing) into 20 samples each, at a pressing pressure (surface pressure) of 0.25 MPa, and the forming depth was changed in 0.5 mm increments from a forming depth of 0.5 mm, using a rectangular forming die (female die, the surface has a maximum height roughness (nominal value of Rz) of 3.2 μm as specified in Table 2 of the surface roughness standard specimen for comparison in JIS B 0659-1:2002, Annex 1 (Reference)) with an aperture of 32 mm (MD) x 54 mm (TD). The corresponding forming die (male die, the surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the surface roughness standard specimen for comparison in JIS B 0659-1:2002, Annex 1 (Reference)). At this time, the above test sample was placed on the female mold so that the heat-sealable resin layer side was located on the male mold side, and molding was performed. The clearance between the male mold and the female mold was 0.5 mm. The cold-molded sample was irradiated with a penlight in a dark room to confirm whether pinholes or cracks were generated in the aluminum foil by light transmission. The deepest molding depth at which no pinholes or cracks were generated in the aluminum foil in all 20 samples was A mm, and the number of samples at which pinholes or the like were generated at the shallowest molding depth at which pinholes or the like were generated in the aluminum foil was B, and the value calculated by the following formula was determined as the limit molding depth of the battery packaging material. Limit forming depth = A mm + (0.5 mm / 20 pieces) x (20 pieces - B pieces)

[0188] [Table 2]

[0189] The battery packaging materials of Examples 1 to 5, in which the thickness of the laminate constituting the battery packaging material is 100 μm or less and the breaking energy of the laminate is 200 J or more in total in one direction perpendicular to the thickness direction of the laminate and in the other direction (perpendicular to the one direction and the thickness direction of the laminate), are found to have excellent moldability. Furthermore, the puncture strength measured from the base layer 1 side of these battery packaging materials was also high.

[0190] Example 6 A barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 35 μm) with an acid-resistant film formed on both sides was laminated on a biaxially oriented nylon film (thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil with an acid-resistant film formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.

[0191] Next, on the barrier layer of the obtained laminate, maleic anhydride modified polypropylene (thickness 14 μm) as an adhesive layer and polypropylene (thickness 10 μm) as a heat-sealable resin layer were co-extruded to laminate an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material (total thickness 87 μm) in which a biaxially oriented nylon film (25 μm) / adhesive layer (3 μm) / barrier layer (35 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated in this order. The laminate configuration of the battery packaging material is shown in Table 3.

[0192] Erucamide was present as a lubricant on both sides of the obtained battery packaging material to form a lubricant layer.

[0193] Example 7 A barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) with acid-resistant coating formed on both sides was laminated on a biaxially oriented nylon film (thickness 25 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil with acid-resistant coating formed on both sides, and an adhesive layer (thickness after curing 2 μm) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.

[0194] Next, on the barrier layer of the obtained laminate, maleic anhydride modified polypropylene (thickness 14 μm) as an adhesive layer and polypropylene (thickness 10 μm) as a heat-sealable resin layer were co-extruded to laminate an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material (total thickness 91 μm) in which a biaxially oriented nylon film (25 μm) / adhesive layer (2 μm) / barrier layer (40 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated in this order. The laminate configuration of the battery packaging material is shown in Table 3.

[0195] As in Example 6, erucic acid amide was added as a lubricant to form a lubricant layer on both sides of the obtained battery packaging material.

[0196] Example 8 A barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) with acid-resistant coating formed on both sides was laminated on a biaxially oriented nylon film (thickness 15 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil with acid-resistant coating formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.

[0197] Next, on the barrier layer of the obtained laminate, maleic anhydride modified polypropylene (thickness 20 μm) as an adhesive layer and polypropylene (thickness 15 μm) as a heat-sealable resin layer were co-extruded to laminate an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material (total thickness 93 μm) in which a biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (20 μm) / heat-sealable resin layer (15 μm) were laminated in this order. The laminate configuration of the battery packaging material is shown in Table 3.

[0198] As in Example 6, erucic acid amide was added as a lubricant to form a lubricant layer on both sides of the obtained battery packaging material.

[0199] Example 9 A barrier layer made of aluminum foil (JIS H4160:1994 A8021H-O, thickness 40 μm) with acid-resistant coating formed on both sides was laminated on a biaxially oriented nylon film (thickness 15 μm) as a base layer by dry lamination. Specifically, a two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to one side of the aluminum foil with acid-resistant coating formed on both sides, and an adhesive layer (thickness 3 μm after curing) was formed on the aluminum foil. Next, the adhesive layer on the aluminum foil and the biaxially oriented nylon film were laminated, and then aging treatment was performed to produce a laminate of base layer / adhesive layer / barrier layer.

[0200] Next, on the barrier layer of the obtained laminate, maleic anhydride modified polypropylene (thickness 14 μm) as an adhesive layer and polypropylene (thickness 10 μm) as a heat-sealable resin layer were co-extruded to laminate an adhesive layer / heat-sealable resin layer on the barrier layer. Next, the obtained laminate was aged and heated to obtain a battery packaging material (total thickness 82 μm) in which a biaxially oriented nylon film (15 μm) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (14 μm) / heat-sealable resin layer (10 μm) were laminated in this order. The laminate configuration of the battery packaging material is shown in Table 3.

[0201] As in Example 6, erucic acid amide was added as a lubricant to form a lubricant layer on both sides of the obtained battery packaging material.

[0202] [Table 3]

[0203] In Table 3, the numerical values ​​in the laminated structure indicate thickness (μm). Furthermore, ONy indicates a biaxially oriented nylon film, DL indicates an adhesive layer or a bonding layer formed by a dry lamination method, ALM indicates an aluminum foil, PPa indicates an adhesive layer formed from maleic anhydride-modified polypropylene, PP indicates a heat-sealable resin layer formed from polypropylene, and CPP indicates a heat-sealable resin layer formed from non-oriented polypropylene (CPP).

[0204] <Measurement of thickness of laminate> The thickness of the laminate constituting each of the battery packaging materials obtained in Examples 6 to 9 was measured in the same manner as in Examples 1 to 5 and Comparative Examples 1 to 3. The results are shown in Table 4.

[0205] <Puncture strength of laminate> The puncture strength of each of the battery packaging materials obtained in Examples 6 to 9 was measured from the base layer side by a method conforming to the provisions of JIS Z1707:1995 in the same manner as in Examples 1 to 5 and Comparative Examples 1 to 3. The results are shown in Table 4.

[0206] <Break energy of laminate> For each of the battery packaging materials obtained in Examples 6 to 9, the breaking energy of the laminate was measured in the same manner as in Examples 1 to 5 and Comparative Examples 1 to 3. The results are shown in Table 4.

[0207] <Evaluation of curl due to molding> Each battery packaging material obtained in Examples 6 to 9 was cut into a rectangular strip measuring 150 mm in the transverse direction (TD) × 90 mm in the machine direction (MD), which was used as a test sample. A 31.6 mm × 54.5 mm rectangular male mold (surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece in JIS B 0659-1:2002, Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) and a female mold with a clearance of 0.3 mm between the male mold and the rectangular male mold (surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece in JIS B 0659-1:2002, Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) were cut into a rectangular strip measuring 150 mm in the transverse direction (TD) × 90 mm in the machine direction (MD), which was used as a test sample. The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard piece is 3.2 μm. Using a mold having corner R2.0 mm, ridge R1.0 mm), the above test sample was placed on the female mold so that the heat-sealable resin layer side was located on the male mold side, and the test sample was pressed with a pressure (surface pressure) of 0.25 MPa so that the test sample had a size of 31.6 mm (MD) × 54.5 mm (TD) and a molding depth of 6 mm, and cold molding (pulled in one-stage molding) was performed. The details of the position where molding was performed are as shown in FIG. 8. As shown in FIG. 8, molding was performed at a position where the shortest distance d between the rectangular molded part M and the end P of the battery packaging material 10 was 70.5 mm. The molded part M indicates the position where a recess is formed by the mold. Next, the molded battery packaging material 10 was placed on a horizontal plane 20 as shown in FIG. 9, and the maximum value t of the vertical distance y from the horizontal plane 20 to the end P was taken as the maximum height of the curled part. The curl due to molding is smaller the value, and the better the material is as a packaging material for batteries. The results are shown in Table 4.

[0208] <Evaluation of moldability> The moldability of each of the battery packaging materials obtained in Examples 6 to 9 was evaluated in the same manner as in Examples 1 to 5 and Comparative Examples 1 to 3. The results are shown in Table 4.

[0209] <Molding depth at which the barrier layer becomes 20 μm thick> Each battery packaging material obtained in Examples 6 to 9 was cut into a rectangular strip with a length (MD) of 90 mm and a width (TD) of 150 mm, which was used as a test sample. A rectangular male mold with a length (MD) of 31.6 mm and a width (TD) of 54.5 mm (the surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002 Annex 1 (Reference), corner R2.0 mm, ridge R1.0 mm) and a female mold with a clearance of 0.3 mm from the male mold (the surface has a maximum height roughness (nominal value of Rz) of 1.6 μm as specified in Table 2 of the comparative surface roughness standard piece of JIS B 0659-1:2002 Annex 1 (Reference)), were placed in contact with the female mold. The maximum height roughness (nominal Rz value) of the comparative surface roughness standard piece is 3.2 μm as specified in Table 2. Using a straight mold with a corner R2.0 mm and a ridge R1.0 mm, the above test sample was placed on the female mold with the heat-sealable resin layer side of the test sample positioned on the male mold side, and the test sample was pressed with a pressing pressure (surface pressure) of 0.25 MPa to perform cold molding (one-stage drawing molding).

[0210] Using this cold forming method, forming was performed successively under conditions in which the forming depth was increased by 0.5 mm from 2.0 mm, and the relationship between the thickness a of the corner P of the barrier layer of the formed test sample (see FIG. 9) and the forming depth was plotted and an approximate straight line was drawn to create a graph. From the graph, the forming depth at which the thickness a of the corner P of the barrier layer became 20 μm was determined.

[0211] The thickness a of the barrier layer of the test sample after molding was measured by cutting the battery packaging material in the thickness direction with a microtome (REM-710 ritratome manufactured by Yamato Koki Kogyo Co., Ltd.) on a straight line connecting the mutually opposing corners P of the part protruding in a substantially rectangular shape when the test sample was viewed in plan from the base layer side, and observing the cross section of the corner P of one of the divided test samples with a laser microscope (VK-9700 manufactured by Keyence Co., Ltd.). One of the divided test samples had two corners, and the thickness a of the barrier layer was taken as the average value of the thicknesses a of the barrier layer at these corners. A schematic diagram of the barrier layer of the test sample after molding is shown in FIG. 10. The position of the thickness of the corner P is the position where the radius of curvature of the corner P (curved part) formed by molding is the smallest, and usually means the center part from the start to the end of the curvature.

[0212] [Table 4] [Explanation of symbols]

[0213] 1 Base material layer 2 Adhesive layer 3. Barrier layer 4 Heat-fusible resin layer 5 Adhesive layer 6 Surface coating layer 7 Colored layer

Claims

[Claim 1] The laminate includes at least a base layer, a barrier layer, and a heat-sealable resin layer in this order. The thickness of the laminate is 100 μm or less, The laminate is subjected to a tensile test under the following test conditions, and the breaking energy per unit width of 1 m is calculated from a curve of a measured load (N / 15 mm) vs. a displacement amount measured. The breaking energy per unit width of the laminate is calculated from a curve of a measured load (N / 15 mm) vs. a displacement amount measured under the following test conditions ... (Test conditions) Test speed: 50 mm / min Test piece width: 15 mm Gauge distance: 30mm

Citation Information

Patent Citations

  • Layered package material, outer package material for battery, and the battery

    JP2008287971A